Particulate matter 2.5 promotes HIF-1α-associated autophagy and epithelial–mesenchymal transition in 3D retinal pigment epithelial spheroids - Da Hye Kim; EunJin Bang; Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; Hyesook Lee; Su Hyun Hong; Gi Young Kim; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Experimental and analytical investigations of composite girders with CSW-CFST chord-UHPC slab under impact loading - Wei Xian; Shuang-Shuang Li; Wen-Da Wang; Yan-Li Shi; Wei-Hong Wu; Wensu Chen (Engineering Structures, 2026)

Recombinant Amuc_1100 from Akkermansia muciniphila modulates tight junction-associated protein in vaginal epithelial cells - Da Won Lee; Chae Eun Lee; Jong Seok Lim; Sohee Lim; Soon Auck Hong; Hye Jun Lee; Jin-Won Chung; Soon Chul Myung (Archives of Microbiology, 2026)

Physiological and molecular mechanisms of blue light-regulated archeospore formation in Pyropia yezoensis - Li-Fei Yang; Yue-Ting Pan; Hong-Chang Ding; Da-Hai Gao (Aquaculture, 2026)

Structure-dependent regulation of nanoplastic uptake by humic substances in a freshwater protozoan - Ke-Da Zhang; Hong-Jie Zhang; Xin-Yuan Li; Wei Pan; Xin-Lei Wang; Ai-Jun Miao (Water Research, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Development and optimization of analytical methods for rapid detection of multiple mycotoxins in wheat products and dietary risk assessment - Kuan-Hsun Li; Mei-Jen Huang; Tomohisa Ogawa; Tseng-Yu Tsai; Hong-Da Hua; Deng-Jye Yang (Food Chemistry, 2026)

Borehole geophysical studies in glaciers. Part II: Borehole in situ observatories - Pavel G. Talalay; Xiaopeng Fan; Bing Li; Nan Zhang; Da Gong; Jialin Hong; Yazhou Li (Earth-Science Reviews, 2026)

Low-loss AgReMo2O8 (Re = Y, Yb) LTCC ceramics designed by Ag+ common-ion effect for dielectric resonator antenna applications - Jian Bao; Jing Guo; Da Tian; Zhen Fang; Zhen-Tao Wang; Yang Liu; Yang Gao; Cai-Hong Zhang; Biao-Bing Jin; Andreu Cabot; Li-Xia Pang; Kar Ban Tan; et al. (Chemical Engineering Journal, 2026)

Sensitive fluorescent europium-organic framework sensor for selective discrimination of tetracycline and norfloxacin and applications in food samples - Chaodan Xiong; Liping Ren; Qiu-Hong Cheng; Xiang-Yu Zhang; Lijuan Liang; Kun Huang; Da-Bin Qin (Food Chemistry, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

DSTs may affect the swimming ability of marine medaka by interfering with the neurotransmitter system and calcium signaling - Zi-min Chen; Mei-qi Li; Jing-xuan Jiang; Yan-hang Mo; Da-wei Li; Hong-ye Li; Wei-dong Yang (Environmental Pollution, 2026)

Selective rare earth element recovery via redox–coordination intercalation in polymer-functionalized flow-electrode capacitive deionization - Hyuncheal Lee; Da Yun Kwon; Jihun Lim; Juhyung Lee; Seungkwan Hong (Desalination, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Evaluation of calcined oyster shell waste as a sustainable dietary calcium source for juvenile black rockfish (Sebastes schlegelii): Effects on growth performance, digestive enzyme activity, antioxidant defense, and innate immune responses - Tae Hoon Lee; Jeoung Eun Park; Hwa Yong Oh; Da Ye Kang; Young Wook Kim; Do Hyun Kwon; Bo Seong Gu; Dona Thilini Udarika Samaraweera; Hyun-Ki Hong; Gun Wook Baeck; Jae-Suk Choi; Hee Sung Kim (Animal Feed Science and Technology, 2026)

A comparative analysis of regulatory frameworks and their market impacts on health functional foods: perspectives from South Korea, Canada, the United States, and China - Da-Eun Min; Dal Eum Han; Kwonsoo Kang; Ke Ding; Guangpeng Xu; Mi-Young Lee; Dong Sung An; Nayon Hur; Jin Man Kim; Ji Youn Hong; Bok Kyung Han; Martin J. T. Reaney; et al. (Critical Reviews in Food Science and Nutrition, 2026)

UAV-based hyperspectral imaging and deep learning for mapping fouling-related water quality indicators in seawater desalination during HABs - Da Yun Kwon; Hyuncheal Lee; Jiaqi Yin; Seungkwan Hong (Water Research, 2026)

Annexin A2 orchestrates CSFV entry route selection via the annexin A2/S100A10 heterotetrameric complex - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Jiaoyang Li; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; et al. (Veterinary Microbiology, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Benzophenone-type UV filters in aquatic ecosystems: Sources, toxicological impacts, and interactions with coexisting stressors - Yu Ri Jin; Mi-Song Hong; Jin-Sol Lee; Jiezhang Mo; Piotr Maszczyk; Menghong Hu; Youji Wang; Zhou Yang; Minghua Wang; Da-Zhi Wang; Min-Chul Lee; Jae-Seong Lee (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Correction: MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

Seismic behavior of precast concrete beam-column joints with an innovative non-porous grouted sleeve connection - Hong Chang; Yi Yuan; Guanda Liu; Da Xu; Renwei Ma (Bulletin of Earthquake Engineering, 2026)

Short-term time series predictions of greenhouse gas emission from dairy houses based on diverse machine learning models - Xiong Shen; Shilin Ming; Wentao Wu; Dong Xie; Huimin Yao; V. Vishnupriya; Hong Zhang; Chen Da; Guoqiang Zhang (Computers and Electronics in Agriculture, 2026)

Molecular epidemiology and genetic diversity of carp edema virus (CEV) in China (2013–2019): New insights into transmission and diagnosis - Tinhan Chien; Chuwei Ma; Junqi Wang; Weizhong Tian; Shifu Kan; Xuebing Yang; Shaolin Tang; Meiting Lee; David Stone; Sophie St-Hilaire; Hsien-Da Huang; Hong Liu; et al. (Aquaculture, 2026)

A novel PGPR Streptomyces sp. for efficient phthalate biodegradation: Mechanistic insights and application in contaminated soil - Hong-Jia Huang; Yi-Tong Huang; Miao Xin; Xiao-Qiong Zhu; Hui LYU; Jiayu Hu; Lei Xiang; Yan-Wen Li; Hai-Ming Zhao; Quan-Ying Cai; Meng Li; Da-Wei Li; et al. (Journal of Hazardous Materials, 2026)

Elucidation of caffeine degradation in kombucha by Komagataeibacter saccharivorans KS1 and low-caffeine kombucha production - Da-Eun Jang; Seong-Jin Hong; Ki-Nam Yoon; Hye-Jin Kang; Ok Cheol Kim; Young-Min Kim (Food Bioscience, 2026)

Machine learning-based prediction of multispecies fisheries catch in relation to environmental factors along the southern coast of Korea - Onyu Ha; Da Yun Kwon; Seungkwan Hong (Regional Studies in Marine Science, 2026)

A green approach to photocatalysis: Silk-sericin-exfoliated MoS2 modified silk fabric for degradation of doxorubicin and textile wastewater - Marimuthu Suriya; Ravichandran Jayachitra; Adhimoorthy Prasannan; Varghese Lincy; Hsieh-Chih Tsai; Po-Da Hong (Journal of Cleaner Production, 2026)

Geniposide ameliorates DSS-induced colitis via synergistically restoring intestinal barrier integrity and inhibiting the NF-κB-NLRP3-pyroptosis axis - Ximing Yang; Da Hong; Xiaoyu Ma; Yijiu Zhang; Li Liu; Shuzhen Cheng (Food Bioscience, 2026)

Lactoferrin-derived hydrophobic peptide YIYT alleviates osteoporosis via synergistic activation of Wnt/β-catenin and BMP/Smad pathways - Zhihui Chang; Da Hong; Xiaoyu Ma; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

Tm4sf19 inhibition alleviates imiquimod-induced psoriatic dermatitis by regulating inflammatory signaling pathways and keratinocyte proliferation in mice - Min Gi Kang; Sujin Park; Eunji Hong; Min-Jung Lee; Da Seul Jung; Jin Sun Heo; Haein An; Min Woo Kim; Naim Park; Hyeyeon Park; Pyunggang Kim; Minjung Son; et al. (Inflammation Research, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Optimization and validation of a TaqMan real-time PCR for the detection of Heterobilharzia americana in dog feces - Francis Aduku; Jody L. Gookin; Jan S. Suchodolski; Lea J. Poellmann; Joe L. Luksovsky; Guilherme G. Verocai; Luis Fernando da Costa Medina; Mike Hong; Kathleen M. Aicher (Veterinary Parasitology, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Multicolor vanadium dioxide-polyvinylpyrrolidone/silver bilayer smart films for reconfigurable visible color and solar energy modulation - Yoonjoo Choi; Byoungsu Ko; Hyungyoon Choi; Giyong Park; Sunga Kim; Ho Young Woo; Da Won Lee; Ran An; Yerin Kim; Sung-Hoon Hong; Junsuk Rho; Tianshuo Zhao; et al. (Chemical Engineering Journal, 2026)

Whole-genome Resequencing Reveals the Sex Determination System and Develops a Sex-specific Marker in Fat Greenling (Hexagrammos otakii) - Duan Liao; Yangqing Zhang; Chunlong Miao; Shuo Li; Weijing Li; Chen Li; Ivana Felipe da Rosa; Lucas Benites Doretto; Yuyan Liu; Qian Wang; Kaiqiang Liu; Hong-Yan Wang; et al. (Marine Biotechnology, 2026)

Mantle dunites archive multistage melt metasomatism under a fossil slow-ultraslow spreading center: an example from the Tibetan Xigaze ophiolite - Li Wang; Qing Xiong; Hong-Kun Dai; Xiang Zhou; Hong-Da Zheng; Hao-Qin Sun; Yi-Cong Li; Long-Fei Xue; Alessio Sanfilippo; Valentin Basch; Jian-Ping Zheng (Contributions to Mineralogy and Petrology, 2026)

Validation and predictive application of a single-parameter analytical model for saltwater intrusion in the Modaomen Estuary - Zhilin Zhang; Guangling Huang; Da Liu; Changhong Hong (Acta Oceanologica Sinica, 2026)

Physiological and transcriptomic responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to multiple environmental factors - Can-Jun Cai; Wei-Ping Zhang; Zi-Cheng Dong; Ye-Hong Xin; Zhang-Xian Xie; Shu-Feng Zhang; Da-Zhi Wang (Water Research, 2026)

Prolonged low pH reprograms carbon and nitrogen metabolism and micronutrient use in Symbiodinium kawagutii and reveals indicators for reef water quality management - Fu-Fang Wen; Qing-Ling Ma; Hao-Ran Guo; Yan Huang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Environmental Research, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Direct seawater electrolysis for Mg(OH)2 extraction over an anti-scaling cathode with NiFeCo hierarchical microstructure arrays - Wei Long Wang; Wei Hao Zhong; Fan Xia; Wen Da Kang; Yu Wei Gu; Yu Chen Zhao; Hong Yi Sheng; Hong Tao Yu (Chemical Engineering Journal, 2026)

Yak dung generates lower soil N retention and stimulates higher N2O emissions relative to Tibetan sheep dung in an alpine meadow on the Eastern Qinghai-Tibetan Plateau - Zhaoyang Xiong; Xiaodan Wang; Yanjiang Cai; Da Wei; Jian Sun; Jiangtao Hong; Yongheng Gao; Xue Zhang; Ying Cao; Huan Qian; Yaxian Guo; Ziyin Du (Plant and Soil, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Efficacy of copper alloy coatings in controlling Ichthyophthirius multifiliis infections: a sustainable alternative for freshwater aquaculture - Zi-Hong Guo; Wen-Hao Wu; Ming-Da Chen; Zi-Jian Long; Jian-Cheng He; Jia-Hao Zhang; You-Lu Su; Biao Jiang (Aquaculture, 2026)

ANXA2 stabilizes mTOR at the plasma membrane to facilitate autophagic flux for CSFV release - Tao Wang; Liangcai Da; Junfang Zhao; Hong Yuan; Ying Sun; Liang Zhang; Kun Li; Jing Zhang; Pu Sun; Zhixun Zhao; Qiang Zhang; Yuanji Zhang; et al. (Veterinary Microbiology, 2026)

Molecular insights into the adsorption and fractionation of dissolved organic phosphorus induced by lanthanum-activated hydrogel - Shuai Liu; Fengjuan Yang; Changhong Hong; Da Liu; Yanpeng Cai; Shengrui Wang (Journal of Environmental Chemical Engineering, 2026)

Energy efficiency and thermochemistry of sulfur-containing coal gangue, a coal-based solid waste - Hui-yong Niu; Chen-hong Zhou; Hai-yan Wang; Gong-da Wang; Jiu-ling Zhang; Yan-xiao Yang; Xiaodong Yu (Fuel, 2026)

Enhanced hydrolysis of cellobiose using vanadium-doped niobium phosphate: A water-tolerant solid acid catalyst with superior kinetic performance - Da-Ming Gao; Jianxing Zheng; Cheng-Bin Hong; Tong Wang; Xue-Chen Xu; Hidemi Fujino; Haichao Liu (Fuel, 2026)

Acrylonitrile exposure incurs lung function decline: Insights from lifestyle intervention and mechanistic pathway in an urban prospective cohort - Shuhui Wan; Jiahao Song; Yongfang Zhang; Yueru Yang; Da Shi; Xiaojie You; Ruyi Liang; Le Hong; Qing Liu; Zhiying Huo; Wei Liu; Wendi Shi; et al. (Environmental Research, 2026)

A techno-economic review of emerging membrane contactor technologies for environmental applications: Performance, limitations, and future directions - Seonkyu Lee; Jaewon Lee; Da Yun Kwon; Onyu Ha; Juhyung Lee; Jiuk Kwon; Junghyun Kim; Seungkwan Hong (Chemical Engineering Journal, 2026)

Cross National study on landslide awareness and risk management - Sabab Aosaf; Safiyeh Tayebi; Ana Lorena Ruano; Gwenyth O. Lee; Paula F. da Silva; Moeen Hamid Bukhari; Saleh Ahmed; M. Atiqur Rahman; Ala Uddin; Jian-Hong Wu; M. Sohel Rahman; Ubydul Haque (Natural Hazards, 2026)
Coastal communities are facing growing landslide risks due to climate change, with variable rainfall patterns exacerbating their vulnerability. Landslides result in significant casualties and economic losses, highlighting the need to better understand community perceptions and responses. This study analyzed landslide preparedness and response in coastal communities of Bangladesh, Portugal, and Taiwan. Open-ended questionnaires were distributed to residents in areas prone to landslides. Data were further analyzed using computational topic modeling to extract core themes and decision tree analysis to predict adaptation behaviors based on influencing factors. Findings reveal distinct vulnerabilities and adaptive capacities in each study site, emphasizing the importance of tailored strategies for disaster risk reduction. Socio-economic variables such as education, employment status, and community shaped perceptions of landslide risk perception and mitigation behaviors. Varying levels of trust between countries had implications for the effectiveness of response strategies. This cross-national comparison advances global efforts to strengthen adaptation and reduce risks in landslide-prone coastal regions. Our findings underscore the need for tailored, community-specific disaster management strategies and highlight the value of integrating socio-demographic factors into risk assessment and mitigation planning.

Plant-derived CD200-Fc promotes tight junction integrity in bladder epithelial cells - Da Won Lee; Jeong Hwan Lee; Chae Eun Lee; Jong Seok Lim; Sohee Lim; Jin Wook Kim; Soon Auck Hong; Min Eui Hong; Joo Young Kim; Hye Jun Lee; Kisung Ko; Soon Chul Myung (Plant Biotechnology Reports, 2026)

Pollen-Specific OsRALF5 Regulates Pollen Tube Growth in Oryza sativa - Hyo-Jeong Kim; Ji-Hyun Kim; Eui-Jung Kim; Ye-Jin Son; Woo-Jong Hong; Da Eun Kim; Byoung Il Je; Ki-Hong Jung; Yu-Jin Kim (Journal of Plant Biology, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Distribution and correlation of trace elements in Eurasian otters (Lutra lutra) from South Korea - Da Sol Park; Eun Jae Park; Dahye Shin; Rihyun Kim; Bongkyun Kim; Yongsun Hyun; Hee-Jong Kim; Kyu-Vin Kim; Chang Uk Chung; Dong-Hyuk Jeong; Jong Seung Kim; Ju Yeong Park; et al. (Environmental Science and Pollution Research, 2026)

Asthenosphere-crust interactions in a continental-subduction channel: Records from UHP peridotite-hosted pyroxenites - Si-Yi Cao; Qing Xiong; Jian-Ping Zheng; Hong-Kun Dai; Qiang Ma; Wen Zhang; Hong-Da Zheng; Hao-Qin Sun; William L. Griffin; Suzanne Y. O'Reilly (Lithos, 2026)

Bacteriophage emulsion for prevention of Salmonella contamination in eggshells - Su Jin Jo; Sang Guen Kim; Sib Sankar Giri; Sung Bin Lee; Jae Hong Park; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Se Chang Park (International Journal of Food Microbiology, 2026)

EED226 treatment targets key immune genes to suppress LPS response in Chinese tongue sole splenocytes - Yangqing Zhang; Lei Lin; Duan Liao; Shengyu Zhu; Yanan Li; Lucas Benites Doretto; Ivana Felipe da Rosa; Yajun Wang; Hong-Yan Wang; Changwei Shao (Fish & Shellfish Immunology, 2026)

Effect of papaya leaf extract on growth performance, skin mucosal immune responses, liver enzymes, disease resistance, and tight junctions of Cyprinus carpio - Sib Sankar Giri; Jin Woo Jun; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Jae Hong Park; Da Sol Park; Eun Jae Park; Venkatachalam Sukumaran; Se Chang Park (Fish & Shellfish Immunology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Buccal application of microneedles coated with an optimized hydrogel containing naproxen and dexamethasone - Joo-Young Kim; Yun-Sik Um; Young-Guk Na; Da-Eun Kim; Yo Han Song; Suyeon Hwang; Minki Jin; Jooyoung Kim; Seung-Ki Baek; Jong-Suep Baek; Hong-Ki Lee; Cheong-Weon Cho (Drug Delivery and Translational Research, 2026)

A plasticity model for plate anchors under V-H combined loading in sand considering fabric anisotropy - Yi Hong; Yixuan Hu; Lizhong Wang; Xuetao Wang; Zhiwei Gao; Shuzhao Li; Da Li (Computers and Geotechnics, 2025)

Receptor affinity-selective differential dynamics of membrane fusion initiation govern deltacoronavirus cross-species transmission - Da An; Qi Peng; Yong-Hao Ma; Wenguang Hong; Yi Pei; Shiyu Liu; Yan Li; Jizong Li; Yanke Shan; Yulong Yin; Bin Li; Fei Liu (Science China Life Sciences, 2025)

Associations between Plasma Metal Concentrations and Mortality Risk in Non-Small-Cell Lung Cancer Patients: A Prospective Cohort Study - Yan Liu; Xiao-Yun Chen; Jing-si Chen; Miao Xu; Hong-Jun Zhang; Quan Tang; Yu‑Song Zhang; Da‑Peng Li; Li-Qiang Qin; Kun Wang (Biological Trace Element Research, 2025)

Unleashing the potential of biotechnological strategies for the sustainable production of microalgal polysaccharides - Srinivasan Balamurugan; Da-Wei Li; Xiang Wang; Hong-Ye Li (Critical Reviews in Food Science and Nutrition, 2025)

Improvement of RNAi efficiency by delivering of dsRNA formulated with cell-penetrating disulfide polymer in the fall Armyworm, Spodoptera frugiperda - Xu Wu; Wen-Mei Li; Qiang Xu; Xiao-Ping Yi; Da-He Zhang; Ming-Zhe He; Yu-Hong Ren (Journal of Insect Physiology, 2025)

Bioconversion and characteristics of the rebaudioside D-like compound by glucosyltransferases combination - Hye-Jin Kim; Ok Cheol Kim; Seong-Jin Hong; Hye-Jin Kang; Da Eun Jang; Boo-Su Park; Jeong-Yong Cho; Young-Min Kim (Food Chemistry, 2025)

Effect of Illicium verum Hook.f. (star anise) extract on the modulation of systemic and mucosal immunity in Aeromonas hydrophila-aggravated Cyprinus carpio - Sib Sankar Giri; Hyoun Joong Kim; Subrata Saha; Jae Hong Park; Sung Bin Lee; Su Jin Joo; Mae Hyun Hwang; Da Sol Park; Eun Jae Park; Kihae Ra; Sukumaran Venkatachalam; Se Chang Park (Fish & Shellfish Immunology, 2025)

A dynamic prediction model for maximum lateral displacement of foundation pit enclosure structure using multi-source fusion method - He Wei Kuang; Zhi Yong Ai; Gan Lin Gu; Hong Wei Huang; Zeng Zhi Qian; Da Xing Zhou; Yu Xin Zhai; Hai Feng Guo (Computers and Geotechnics, 2025)

Integrative machine learning and molecular insights into ZEN degradation by Apiotrichum mycotoxinivorans - Zhi-Kai Yang; Yun Huang; Xue-Ling Huang; Dan Huang; Liang Peng; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Chemical Engineering Journal, 2025)

Designing interfacial edge microenvironments of cobalt phosphide quantum dots/graphitic carbon nitride to modulate electron delocalization for ultrafast photocatalytic hydrogen evolution - Xiukun Hu; Yunxiong Zeng; Heng Liu; Bo Da; Hao Li; Bo Hong; Xiaoling Peng; Xinqing Wang (Chemical Engineering Journal, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Siloxene coupled graphene anode membrane with Zn-ion intercalation for all-solid-state Zn-ion hybrid supercapacitors - Erhui Zhang; Da Xie; Yuchen Hong; Zhenzhen Hui; Yongsheng Zhou; Shengbiao Zheng; Jiahao Guo; Zirong Li; Jie Chen; Jing Tang (Chemical Engineering Journal, 2025)

Model Construction and Research of Synergistic Effect Mechanism on Subglacial Bedrock Core Breaking - Rusheng Wang; Zhihao Cui; Guigang Tu; Xiaopeng Fan; Da Gong; Siqi Hong; Xinyu Lv (Rock Mechanics and Rock Engineering, 2025)

Detection of the intergenic region III and multigene family 505 9R and 10R-V variant of African swine fever virus genotype II on pig farms in South Korea - Ki-Hyun Cho; Da-Young Kim; Seong-Keun Hong; Dae-Sung Yoo; Hae-Eun Kang; Yeon-Hee Kim (Archives of Virology, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Toxicokinetic-toxicodynamic modeling reveals the ecological risks of differently-sized polystyrene nanoplastics - Ke-Da Zhang; Zhen Wang; Hong-Jie Zhang; Hai-Tao Fang; Qiao-Guo Tan; Ai-Jun Miao (Environmental Pollution, 2025)

Multidimensional mechanism investigation on improving the pretreatment performance and enzymatic saccharification of bamboo with choline chloride-based deep eutectic solvents - Yu Sheng; Yao-yao Jin; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Tao-hong Li; Jing Yang (Chemical Engineering Journal, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Ten questions on building stock modeling to inform energy efficiency and sustainability - Tianzhen Hong; Jeetika Malik; Jared Langevin; Zhaoru Liu; Da Yan (Building and Environment, 2025)

Ten questions concerning calibrating building energy simulation models - Adrian Chong; Da Yan; Kaiyu Sun; Sicheng Zhan; Siyu Cheng; Yi Wu; Yixing Chen; Tianzhen Hong (Building and Environment, 2025)

Pilot cultivation of a long-type variety in Pyropia suborbiculata (Bangiales, Rhodophyta) - Da-Hai Gao; Yan Zhang; Xing-Hong Yan (Journal of Applied Phycology, 2025)

Engineering hypo-osmotic Crypthecodinium cohnii via SL-ALE for high-yield DHA biosynthesis from agricultural byproducts - Yi-Tong Yao; Yu-He Zhang; Yan Huang; Xiao Zhang; Chen-Yu Wang; Jia-Qi Zheng; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Algal Research, 2025)

Whole genome sequencing reveals telomere associated genomic differences between healthy and unhealthy aging in a Korean population - Ji-Hye Oh; Hyo Jeong Lee; Wonkyung Kim; Da Eun Oh; Hong-Kyu Kim; Eun Hee Kim; Jaewon Choe; Ha Ra Jun; Chae Won Park; Young Gwang Kang; Chong Jai Kim; Chang Ohk Sung; et al. (Biogerontology, 2025)

Insights Into the Separate and Joint Effects of Cadmium and Cesium on the Risk of Circadian Syndrome and the Underlying Mechanism: An Integrated Epidemiological and Network Toxicological Study - Zhiying Huo; Wei Liu; Qiang Sun; Jiahao Song; Shuhui Wan; Wendi Shi; Yueru Yang; Le Hong; Qing Liu; Yongfang Zhang; Da Shi; Weihong Chen; et al. (Biological Trace Element Research, 2025)

Volatile organic compounds exposure, biological ageing, and increased sarcopenia risk: Association, interaction, and mechanistic exploration - Le Hong; Qing Liu; Wei Liu; Jiahao Song; Shuhui Wan; Zhiying Huo; Yongfang Zhang; Da Shi; Ruyi Liang; Bingdong Chen; Yani Xiong; Feifei Wang; et al. (Journal of Hazardous Materials, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

Pluripotent stem cell-derived cardiomyocyte transplantation: marching from bench to bedside - Yi Hong; Jiarui Liu; Weixuan Wang; Hao Li; Weijing Kong; Xiaoxia Li; Wei Zhang; Sara Pahlavan; Yi-da Tang; Xi Wang; Kai Wang (Science China Life Sciences, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Particulate matter 2.5 stimulates pyroptosis and necroptosis via the p38 MAPK/Akt/NF-κB signaling pathway in human corneal epithelial cells - Da Hye Kim; Hyesook Lee; Min Yeong Kim; Hyun Hwangbo; Seon Yeong Ji; EunJin Bang; Su Hyun Hong; Gi Young Kim; Sun-Hee Leem; Dongryeol Ryu; JaeHun Cheong; Yung Hyun Choi (Toxicology, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Recent advances of heteroatom-doped carbon-based materials: Synthesis, properties, environmental application, and catalytic mechanism in advanced oxidation processes - Yinliang Da; Xi Li; Yanghaofan Wang; Guotuan Xie; Siqi Liu; Luyao Zhang; Hong Liang; Yongtao Li; Bing Wang (Journal of Water Process Engineering, 2025)

Portable and miniature sensors in supply chain for food authentication: a review - Hong-Ju He; Marcus Vinicius da Silva Ferreira; Qianyi Wu; Hamed Karami; Mohammed Kamruzzaman (Critical Reviews in Food Science and Nutrition, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

Dual structure Brønsted sites activated carbon beads solid acid enhances the highly efficient synthesis of HMF: From batch to continuous - Wei-Yao Yang; Meng Wen; Hong-Da Zhang; Ya-Qiao Tian; Shi-Chao Su; Yu Lang; Zhi-Ping Zhao; Le Sang (Chemical Engineering Journal, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

A new method for mechanical identification of unstable sliding rock - Yan Du; Hong-da Zhang; Mo-wen Xie; Yu-jing Jiang; Santos Daniel Chicas; Jing-nan Liu (Bulletin of Engineering Geology and the Environment, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Advancing harmful algal bloom detection with hyperspectral imaging: Correlation of algal organic matter and fouling indices based on deep learning - Da Yun Kwon; Do Hyuck Kwon; Jaewon Lee; Jihun Lim; Seungkwan Hong (Desalination, 2025)

Unveiling novel oxygen-dependent docosahexaenoic acid biosynthesis pathway in Crypthecodinium cohnii via dual-function △4-fatty acid desaturases - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Bioresource Technology, 2025)

Anchoring multi-mechanism coupled miniature redox reactors with photothermal foam gels for simultaneous photoreduction U(VI) and interfacial evaporation from wastewater - Jia-Liang Yang; De-Bin Ji; Heng-Yu Tan; Zhi-Qiang Qiao; Zhi-Da Li; Dan-Dan Yuan; Hong-Jun Wu (Journal of Cleaner Production, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Expression and in vitro function of anti-CTLA-4 human antibody expressed in plants - Chae Eun Lee; Jeong Hwan Lee; Hyun Joo Chung; Sohee Lim; Da Won Lee; Jong Seok Lim; Jin Wook Kim; Soon Auck Hong; Min Eui Hong; Joo Young Kim; Hye Jun Lee; Kisung Ko; et al. (Plant Biotechnology Reports, 2025)
Biosimilars produced in plant systems encompass a range of molecules, including antibodies, vaccines, enzymes, receptors, and other therapeutic molecules. In the present study, we aimed to express the immune checkpoint-inhibitor anti-CTLA-4 antibody, Ipilimumab, in Nicotiana tabacum plant. We generated transgenic tobacco plants using Agrobacterium -mediated transformation and purified an anti-CTLA-4 monoclonal antibody (mAb P CTLA-4) using protein A affinity chromatography. This purified mAb P CTLA-4 showed specific binding activity to CTLA-4-positive human tonsil tissues, as confirmed by immunoblot, indirect ELISA, and immunohistochemistry analyses. Our study confirmed that mAb P CTLA-4 effectively targeted CTLA-4 in human tonsil tissues. These findings suggest that our plant-derived anti-CTLA-4 antibody retains its original functionality, underscoring the promising potential of plant-based therapeutic expression systems for producing high-value medicinal biosimilars.

A small RNA effector conserved in herbivore insects suppresses host plant defense by cross-kingdom gene silencing - Wen-Hao Han; Shun-Xia Ji; Feng-Bin Zhang; Hong-Da Song; Jun-Xia Wang; Xiao-Ping Fan; Rui Xie; Shu-Sheng Liu; Xiao-Wei Wang (Molecular Plant, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Tailoring oxygen vacancies of W-doped TiO2 to stabilize Ir for boosting oxygen evolution activity in proton-exchange membrane water electrolysis - Jae-Ik Han; Deok-Hye Park; Da-Mi Lim; Yoonhi Gu; Seon-Ha Park; Chan-Eui Hong; Dong-Geon Seo; Ji-Hwan Kim; Jae-Sung Jang; Eo-Jin Kim; Ji-Woong Yun; Hyun-Moon Jo; et al. (Chemical Engineering Journal, 2025)

Anesthetic Effects of Clove Basil Essential Oil (Ocimum gratissimum) Microemulsion on Asian Redtail Catfish (Hemibagrus wyckioides) and Its Biochemical Stress Indicators - Phuong Hong Lam; Huyen Da Nguyen Vo; Linh My Thi Truong; Dung My Thi Dang; Chien Mau Dang; Tin Chanh Duc Doan; Fatemeh Mollaamin; Majid Monajjemi (Fishes, 2025)
Ocimum gratissimum (clove basil) essential oil is known for its anesthetic and stress-reducing effects in aquatic animals. In this study, it was synthesized into a microemulsion form and its anesthetic effects on Hemibagrus wyckioides (Asian redtail catfish) juveniles were evaluated. The clove basil essential oil was formulated into a stable oil-in-water microemulsion with a particle size of approximately 36.3 nm and a polydispersity index (PDI) of 0.17. The microemulsion, with concentrations ranging from 125 mg L−1 to 250 mg L−1, effectively induced sedation and anesthesia in fish. It took approximately 2 to 4 min for the fish to reach a state of sedation or anesthesia, depending on the concentration of the clove basil essential oil microemulsion used. After a 30 min induction period using clove basil essential oil microemulsion at concentrations of 125 mg L−1 and 175 mg L−1, the blood cortisol, glucose, and lactate levels, which are stress indicators in fish, were evaluated. The results indicated that the blood cortisol levels in the treatments (6.97 to 7.4 μg dL−1) were consistently lower than in the control group (17.17 μg dL−1) throughout the induction time. However, the glucose (5.6–6.75 mmol L−1) and lactate levels (3.23–5.41 mmol L−1) in the treatment groups increased acutely during the induction time but returned to normal levels (around 3.5 mmol L−1 and 1.6 mmol L−1, respectively) during recovery. This contrasted with the control group, where the lactate and glucose levels remained slightly elevated during the recovery period. Additionally, the recovery time in fish anesthetized with clove basil essential oil microemulsion was consistently short across all of the treatments. These findings highlight the potential application of clove basil essential oil, particularly in microemulsion form, as an effective anesthetic agent for fish.

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Ten questions on future and extreme weather data for building simulation and analysis in a changing climate - Da Yan; Yi Wu; Jeetika Malik; Tianzhen Hong (Building and Environment, 2025)

Effect of exogenous abscisic acid on the formation and release of archeospores in Pyropia yezoensis - Li Zhang; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2025)

An image simulator of lunar far-side impact flashes captured from the Earth-Moon L2 point - Da Song; Hong-bo Cai; Shen Wang; Jing Wang (Advances in Space Research, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Metal/organic interface carrier quenching suppression for stable and efficient near-infrared quantum dot light-emitting diodes - Wan-Shan Shen; Yang Liu; Xingtong Chen; Hong-Wei Duan; Jia-Lin Pan; Zhong-Da Zhang; Feng Zhao; Zeke Liu; Sui-Dong Wang; Wanli Ma; Song Chen; Ya-Kun Wang; et al. (Chemical Engineering Journal, 2025)

DQL-assisted competitive evolutionary algorithm for energy-aware robust flexible job shop scheduling under unexpected disruptions - Shicun Zhao; Hong Zhou; Yujie Zhao; Da Wang (Swarm and Evolutionary Computation, 2024)

Remediation of heavy metal contaminated soil in mining areas with vaterite-type biological calcium carbonate - Jun-li Chen; Chang-xiong Zou; Wei-da Wang; Chun-li Zheng; Qing-hong Jiang; Zhe Wang (Process Safety and Environmental Protection, 2024)

Organic matter excreted by the protozoan Tetrahymena thermophila and its effects on the bioaccumulation of nanoparticles - Ke-Da Zhang; Hong-Jie Zhang; Jun-Long Song; Xin-Lei Wang; Wei Pan; Mei Wang; Bin Huang; Liuyan Yang; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Protective mechanism of antioxidant peptides derived from dry-cured ham against ultraviolet A-induced oxidative damage in HaCat cells - Rui-hong Xie; Shan Xiao; Da Ma; Bo Wang; Guan-chao Chen; Jun-han Xiang; Ji-hui Wang (Food Bioscience, 2024)

Exploring the response mechanism of Pseudomonas plecoglossicida to high-temperature stress by transcriptomic analyses for 2-keto gluconic acid production - Da-Ming Wang; Xi Chen; Hao Guo; Qing-Hong Wang; Lei Sun; Wen-Jing Sun (Food Bioscience, 2024)

A tartaric acid (TA)-coated iron-based biochar as heterogeneous fenton catalyst for enhanced degradation of dibutyl phthalate - Xi Li; Guotuan Xie; Xue Gu; Guisen Zhang; Yinliang Da; Yanghaofan Wang; Hong Liang; Yongtao Li; Bing Wang (Environmental Pollution, 2024)

Comparative analysis of the transcriptomes from regenerated plants and root explants of endangered Oplopanax elatus - Ji Won Seo; Hong Ju Choi; Da Ye Ham; Jiu Park; Ik Young Choi; Chang Yeon Yu; Myong Jo Kim; Eun Soo Seong (Genes & Genomics, 2024)

Impacts of aquaculture practices on the sustainability of social-ecological systems in coastal zones of the Mekong Delta - Hieu Hong Hua; Emilie Cremin; Da Van Huynh; Graham Long; Fabrice G. Renaud (Ocean & Coastal Management, 2024)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Lateral transport facilitates terrestrial organic carbon burial in the Santa Barbara Basin over the past 80 years (1937–2018 CE) - Hanyue Xu; Da-Wei Li; Hong-Chun Li; William M. Berelson; Yang Ding; Li Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Understanding the fouling characteristics in ultrafiltration membrane for marine algae-laden seawater pretreatment: Focus on the role of algal extracellular organic matter - Weilong Yang; Feng Zhou; Jaewon Lee; Junghyun Kim; Da Yun Kwon; Youngjin Kim; Hongqiang Ren; Seungkwan Hong; Min Zhan; Bing Wu (Journal of Cleaner Production, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Robust PD/A biofilms sustain advanced real municipal wastewater treatment: Reinforcement of interspecific communication and electron transfer - Xiaonong Zhang; Naif Abdullah Al-Dhabi; Zixuan Zhu; Xingxing Zhang; Li Zhou; Da Jin; Wangwang Tang; Duanliang Hong; Nkonogumo Paul Luchanganya; Hongbo Guo; Peng Wu; Aijie Wang (Chemical Engineering Journal, 2024)

Efficient solution-processable OLEDs near BT.2020 red standard enabled by a multiresonant emitter - Hui Wang; Ying-Chun Cheng; Xiao-Chun Fan; Dong-Yang Chen; Xin Xiong; Xiao-Yao Hao; Yi-Zhong Shi; Jia Yu; Da Huang; Jia-Xiong Chen; Kai Wang; Xiao-Hong Zhang (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Development of Extubation Success Prediction Model for Mechanically Ventilated Patients with Spontaneous Cerebellar Hemorrhage - Yao Jiang; Yue Yu; Jing Fan; Lei Zhang; Yang Ye; Ying-hong Hu; Li-da Su (The Cerebellum, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Shallow-water redox evolution from the Ediacaran to the early Cambrian: Linkages to the early animal innovations - Guang-Yi Wei; Da Li; Zunli Lu; Ganqing Jiang; Hong-Fei Ling (Global and Planetary Change, 2024)

Antibiotics ingestion altered the composition of gut microbes and affected the development and reproduction of the fall armyworm - Yan Fu; Luo-Yan Zhang; Qing-Yi Zhao; Da-Ying Fu; Hong Yu; Jin Xu; Song Yang (Journal of Pest Science, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Cancer risk associated with low-dose ionizing radiation: A systematic review of epidemiological and biological evidence - Shu Min Tao; Le Le Wang; Min Da Li; Jing Wang; Hong Mei Gu; Long Jiang Zhang (Mutation Research - Reviews in Mutation Research, 2024)

Photovoltaic induced self-powered gas sensor based on 2D MoS2 incorporated NbSe2 nanorods heterostructure for NH3 gas sensing at room temperature - Adhimoorthy Saravanan; Bohr-Ran Huang; Seung-Kyu Hwang; Deepa Kathiravan; Wesley Wei-Wen Hsiao; Ravichandran Jayachitra; Abebaw Abun; Po-Da Hong; Ali Mohammadi; A.T. Ezhil Vilian; Young-Kyu Han; Yun Suk Huh (Chemical Engineering Journal, 2024)

Protective Effects of Long Double-Stranded RNA with Different CpG Motifs against Miamiensis avidus and Viral Hemorrhagic Septicemia Virus (VHSV) Infections in Olive Flounder (Paralichthys olivaceus) - Hee-Jae Choi; Da-Yeon Choi; Jung-Jin Park; Hye Jin Jung; Bo-Seong Kim; Sung-Chul Hong; Jun-Hwan Kim; Yue Jai Kang (Fishes, 2024)
The South Korean aquaculture industry has incurred considerable production losses due to various infectious diseases. Artificially synthesized polyinosinic–polycytidylic acid (poly I:C), structurally similar to double-stranded RNA (dsRNA) and cytidine–phosphate–guanosine oligodeoxynucleotides, can enhance immune responses and protect against diseases. Here, we investigated dsRNA molecules with different cytidine–phosphate–guanosine (CpG) motifs (dsRNA-CpGMix) as fused agents to treat Miamiensis avidus and viral hemorrhagic septicemia virus (VHSV) infection in olive flounders. We further investigated the efficacy of specific sequence motifs in dsRNA in modulating immunostimulatory effects. Fish treated with poly I:C or dsRNA-CpGMix exhibited higher survival rates than the control group. Olive flounder leukocytes stimulated with poly I:C or dsRNA-CpGMix showed increased scuticocidal activity in the presence of inactivated immune sera. dsRNA with CpG motif sequences induced higher resistance against M. avidus and VHSV infections than dsRNA without CpG motif sequences, and the dsRNA-CpGMix group showed upregulated ISG15 or Mx compared to the dsRNA-GFP group. Thus, dsRNA containing CpG motifs can be used as effective immunostimulants to enhance resistance against viral and parasitic diseases in olive flounder. The specific sequences of the CpG motifs in dsRNA may be important for enhancing immune responses and resistance against M. avidus and VHSV infections in olive flounders.

Response of the root anatomical structure of Carex moorcroftii to habitat drought in the Western Sichuan Plateau of China - Jia-Ying Yang; Hong-Bin Wang; Da-Cai Zhang (Planta, 2024)
Main conclusion The anatomical structures of Carex moorcroftii roots showing stronger plasticity during drought had a lower coefficient of variation in cell size in the same habitats, while those showing weaker plasticity had a higher coefficient of variation. The complementary relationship between these factors comprises the adaptation mechanism of the C. moorcroftii root to drought. Abstract To explore the effects of habitat drought on root anatomy of hygrophytic plants, this study focused on roots of C. moorcroftii . Five sample plots were set up along a soil moisture gradient in the Western Sichuan Plateau to collect experimental materials. Paraffin sectioning was used to obtain root anatomy, and one-way ANOVA, correlation analysis, linear regression analysis, and RDA ranking were applied to analyze the relationship between root anatomy and soil water content. The results showed that the root transverse section area, thickness of epidermal cells, exodermis and Casparian strips, and area of aerenchyma were significantly and positively correlated with soil moisture content ( P < 0.01). The diameter of the vascular cylinder and the number and total area of vessels were significantly and negatively correlated with the soil moisture content ( P < 0.01). The plasticity of the anatomical structures was strong for the diameter and area of the vascular cylinder and thickness of the Casparian strip and epidermis, while it was weak for vessel diameter and area. In addition, there was an asymmetrical relationship between the functional adaptation of root anatomical structure in different soil moisture and the variation degree of root anatomical structure in the same soil moisture. Therefore, the roots of C. moorcroftii can shorten the water transport distance from the epidermis to the vascular cylinder, increase the area of the vascular cylinder and the number of vessels, and establish a complementary relationship between the functional adaptation of root anatomical structure in different habitats and the variation degree of root anatomical structure in the same habitat to adapt to habitat drought. This study provides a scientific basis for understanding the response of plateau wetland plants to habitat changes and their ecological adaptation strategies. More scientific experimental methods should be adopted to further study the mutual coordination mechanisms of different anatomical structures during root adaptation to habitat drought for hygrophytic plants.

Exploration of anomaly separation technology of wide-field electromagnetic method - Hong-Jun Tian; Zhi-Wen Gu; Guang-Da Zhang; Dong-Dong Zhao; Hao Zhou; Jian Zhang; Bing Guo; Yu-Chen Wang (Applied Geophysics, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Tailored fabrication of biodegradable polymer/ Fe3O4 doped WO3 nano star-based porous membrane with enhanced photo fentonic activity for environmental remediation - Ravichandran Jayachitra; Varghese Lincy; Adhimoorthy Prasannan; J. Nimita Jebaranjitham; Sambasivam Sangaraju; Po-Da Hong (Environmental Research, 2024)

Mechanical Responses of a Porous Red Sandstone to Quasi-Static Cyclic Loads Under Uniaxial Compression - Zhao-Qiang Zheng; Huai-Zhong Liu; Hong-Qiang Xie; Jiang-Da He; Ming-Li Xiao; Li Zhuo (Rock Mechanics and Rock Engineering, 2024)

The simultaneous removal of methylene blue (MB) and Ca2+ by recyclable adsorbents based the scales derived from coal gasification system - Bai-Hong An; Da-Mao Xu; Run-Ting Wang; Ye-Xuan Wen; Rui Geng; Jia-Yun Wu; Xian-Chun Tang; Hong-Bin Chen (Environmental Science and Pollution Research, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Multitasking needle-shaped copper oxide nanorods decorated cystine modified polymer/graphene oxide nanocomposite for 4-nitrophenol reduction, dye degradation, and textile effluent treatment - Ravichandran Jayachitra; J. Nimita Jebaranjitham; Adhimoorthy Prasannan; Varghese Lincy; Sambasivam Sangaraju; Po-Da Hong (Journal of Environmental Chemical Engineering, 2024)

2D Bi2MoO6 nanosheets immobilized on electrospun 1D LaFeO3 hollow nanofibers: An efficacious direct Z-scheme p-n type heterojunction photocatalyst for removal of organic contaminants under visible-light irradiation - Da Xu; Feng Sun; Feng Liu; Hong Shao; Wurigamula He; Lili Wang; Qianli Ma; Wensheng Yu; Hui Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

Intravitreal Delivery of PEGylated-ECO Plasmid DNA Nanoparticles for Gene Therapy of Stargardt Disease - Da Sun; Wenyu Sun; Song-Qi Gao; Jonathan Lehrer; Hong Wang; Ryan Hall; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Bacoside a inhibits the growth of glioma by promoting apoptosis and autophagy in U251 and U87 cells - Hai-Yun Liu; Yu-Long Ji; Hong Du; Shu-Hui Chen; Da-Peng Wang; Qiao-Li Lv (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Estimation of local scour around monopile foundations for offshore structures using machine learning models - Da-Wei Guan; Yu-Xuan Xie; Yee-Meng Chiew; Fan Ding; Tiago Fazeres Ferradosa; Jianhao Hong (Ocean Engineering, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Integrated surrogate framework for reactive transport simulation of uranium in situ leaching with generative models - Wen-gui Ji; Yue Luo; Bing Wang; Xun Li; Jin-hui Liu; Yan-hong Zhang; Da-ye Liang (Journal of Hydrology, 2024)

Elimination method of sliding blockage effect in discrete element simulation of rolling stone based on discrete fracture network and damping joint model - You Zhou; Huai-Zhong Liu; Hong-Qiang Xie; Li Zhuo; Ming-Li Xiao; Jiang-Da He; Jian-Liang Pei; Guo-Wen Xu (Computers and Geotechnics, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Properties and mechanisms of steel slag strengthening microbial cementation of cyanide tailings - Chang-xiong Zou; Meng Xiao; Qing-hong Jiang; Zhe Wang; Chun-li Zheng; Wei-da Wang (Chemosphere, 2024)

The associations between high-levels of urine benzophenone-type UV filters (BPs) and changes in serum lipid concentrations - Qi Chen; Qianyu Chen; Guanyong Su; Da Chen; Zhen Ding; Hong Sun (Chemosphere, 2024)

Diversification of freshwater crabs on the sky islands in the Hengduan Mountains Region, China - Bo-Yang Shi; Da Pan; Kang-Qin Zhang; Tian-Yu Gu; Darren C.J. Yeo; Peter K.L. Ng; Neil Cumberlidge; Hong-Ying Sun (Molecular Phylogenetics and Evolution, 2024)

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Fluid-rock interaction modeling to constrain Au enrichment: Implication for the giant Jiaodong Au mineralization, eastern North China Craton - Huan-Long Hu; Hong-Rui Fan; Ting-Guang Lan; Xue-Feng Yu; Da-Peng Li; Kui-Feng Yang (Gondwana Research, 2024)

Aerated steam eradicates powdery mildew from strawberry transplants - Arne Stensvand; Nan-Yi Wang; Vinh Hong Le; Claudio Dias Da Silva; Belachew Asalf; Chloe Grieu; William W. Turechek; Natalia A. Peres (European Journal of Plant Pathology, 2024)
Powdery mildew, caused by the ascomycete Podosphaera aphanis , is an important disease of strawberry. A slightly modified version of a method using steam thermotherapy to rid diseases and pests from strawberry transplants was tested against strawberry powdery mildew. Experiments took place in Norway and Florida, with potted strawberry plants heavily infected with the fungus. Aerated steam treatments of the plants were carried out as follows: a pre-treatment with steaming at 37 °C for 1 h was followed by 1 h at ambient temperature before plants were exposed to steaming at 40, 42, or 44 °C for 2 or 4 h in Norway and 44 °C for 4 h in Florida. Following steaming, plants from the different treatments and the untreated control were kept apart and protected from outside contamination of powdery mildew by growing them in closed containers with over-pressure. On steamed plants, hyphae of P. aphanis were dead and without any new spore formation after treatments, independent of temperature or exposure time; however, up to 99% of the area infected with powdery mildew prior to treatments contained actively sporulating lesions on non-steamed plants. None of the new leaves formed after steaming had powdery mildew, whereas more than half of the new leaves on non-treated plants were infected by P. aphanis . This investigation clearly indicates that steam thermotherapy can eradicate powdery mildew from strawberry transplants, and this can be achieved at lower temperatures and exposure times than previously reported for other pathogens.

Advancements of remote data acquisition and processing in unmanned vehicle technologies for water quality monitoring: An extensive review - Da Yun Kwon; Jungbin Kim; Seongyeol Park; Seungkwan Hong (Chemosphere, 2023)

Feasibility study of storing CO2 in the ocean by marine environmental impact assessment - Da Hee Jung; Gyeol Ko; Jin-Su Kwak; Do Yun Kim; Seul Gi Jeon; Seungkwan Hong (Science of The Total Environment, 2023)

Neurotrophic phenolic glycosides from the roots of Armoracia rusticana - Tae Hyun Lee; Da Hye Yoon; Kyoung Jin Park; Seong-Min Hong; Minji Kim; Sun Yeou Kim; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Effects of tillage patterns and stover mulching on N2O production, nitrogen cycling genes and microbial dynamics in black soil - Da-Cheng Hao; Xing-Yuan Su; Hong-Tu Xie; Xue-Lian Bao; Xu-Dong Zhang; Lian-Feng Wang (Journal of Environmental Management, 2023)

Polyphenols modulate microalgae metabolism with a particular increment in lipid accumulation - Li-Gong Zou; Dan-Lin Zheng; Yi-Tong Yao; Fu-Fang Wen; Da-Wei Li; Yu-Feng Yang; Wei-Dong Yang; Srinivasan Balamurugan; Hang Fai Kwok; Hong-Ye Li (Fuel, 2023)

The role of LOXL2 induced by glucose metabolism-activated NF-κB in maintaining drug resistance through EMT and cancer stemness in gemcitabine-resistant PDAC - Yun Sun Lee; Hyung Sun Kim; Hyo Jung Kim; Hyeon Woong Kang; Da Eun Lee; Myeong Jin Kim; Woosol Chris Hong; Ju Hyun Kim; Minsoo Kim; Jae-Ho Cheong; Joon Seong Park (Journal of Molecular Medicine, 2023)
Gemcitabine is considered a standard treatment for pancreatic cancer, but developing drug resistance greatly limits the effectiveness of chemotherapy and increases the rate of recurrence. Lysyl oxide-like 2 (LOXL2) is highly expressed in pancreatic cancer and is involved in carcinogenesis and EMT regulation. However, studies on the role of LOXL2 in drug resistance are limited. Here, we investigated the mechanism of LOXL2 induction and the effect of LOXL2 on EMT and CSC in gemcitabine-resistant pancreatic cancer. Glucose metabolism was activated in gemcitabine-resistant pancreatic cancer cells, and NF-κB signaling was regulated accordingly. Activated NF-κB directly induces transcription by binding to the promoters of LOXL2 and ZEB1. The EMT process was significantly inhibited by the coregulation of ZEB1 and LOXL2. In addition, LOXL2 inhibition reduced the expression of cancer stemness markers and stemness by regulating MAPK signaling activity. LOXL2 inhibits tumor growth of gemcitabine-resistant pancreatic cancer cells and increases the sensitivity to gemcitabine in mouse models. Key messages We identified a specific mechanism for inducing LOXL2 overexpression in gemcitabine-resistant pancreatic cancer. Taken together, our results suggest LOXL2 has an important regulatory role in maintaining gemcitabine resistance and may be an effective therapeutic target to treat pancreatic cancer.

Exposure to per- and polyfluoroalkyl substances in women with twin pregnancies: Patterns and variability, transplacental transfer, and predictors - Songyi Huang; Xiaojie Li; Langjing Deng; Jinying Xie; Guangtong Huang; Chenyan Zeng; Nanxin Wu; Sui Zhu; Chaoqun Liu; Hong Mei; Han Xiao; Da Chen; et al. (Journal of Hazardous Materials, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Cold-water coral diversity along the continental shelf margin of northwestern South China Sea - Mei-Xia Zhao; Yu Zhong; Shu-Qi Zhang; Pu Guo; Da-Peng Jiang; Hong-Qiang Yan; Jian-Wen Qiu; Qi Shi; Duan-Xin Chen (Marine Environmental Research, 2023)

Toxicity and potential underlying mechanism of Karenia selliformis to the fish Oryzias melastigma - Qin-yuan Liu; Zi-min Chen; Da-wei Li; Ai-feng Li; Ying Ji; Hong-ye Li; Wei-dong Yang (Aquatic Toxicology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Effect of boiling on texture of scallop adductor muscles and its mechanism based on label-free quantitative proteomic technique - Zi-Xuan Wu; Yan-Hong Bai; Zi-Ye Wang; Ying-Chen Fan; Liang Song; Yu-Xin Liu; De-Yang Li; Peng-Fei Jiang; Da-Yong Zhou (Food Chemistry, 2023)

Aligning the Global Delta Risk Index with SDG and SFDRR global frameworks to assess risk to socio-ecological systems in river deltas - Emilie Cremin; Jack O’Connor; Sumana Banerjee; Ly Ha Bui; Abhra Chanda; Hieu Hong Hua; Da Van Huynh; Hue Le; Sonia Binte Murshed; Salehin Mashfiqus; Anh Vu; Zita Sebesvari; et al. (Sustainability Science, 2023)
River deltas globally are highly exposed and vulnerable to natural hazards and are often over-exploited landforms. The Global Delta Risk Index (GDRI) was developed to assess multi-hazard risk in river deltas and support decision-making in risk reduction interventions in delta regions. Disasters have significant impacts on the progress towards the Sustainable Development Goals (SDGs). However, despite the strong interlinkage between disaster risk reduction and sustainable development, global frameworks are still developed in isolation and actions to address them are delegated to different institutions. Greater alignment between frameworks would both simplify monitoring progress towards disaster risk reduction and sustainable development and increase capacity to address data gaps in relation to indicator-based assessments for both processes. This research aims at aligning the GDRI indicators with the SDGs and the Sendai Framework for Disaster and Risk Reduction (SFDRR). While the GDRI has a modular indicator library, the most relevant indicators for this research were selected through a delta-specific impact chain designed in consultation with experts, communities and stakeholders in three delta regions: the Red River and Mekong deltas in Vietnam and the Ganges–Brahmaputra–Meghna (GBM) delta in Bangladesh and India. We analyse how effectively the 143 indicators for the GDRI match (or not) the SDG and SFDRR global frameworks. We demonstrate the interconnections of the different drivers of risk to better inform risk management and in turn support delta-level interventions towards improved sustainability and resilience of these Asian mega-deltas.

Environmentally friendly self-assembly strategy to fabricate novel S and O co-doped carbon nitride aerogel photocatalyst with improved photocatalytic degradation capability - Feng Sun; Da Xu; Yunrui Xie; Feng Liu; Haina Qi; Hong Shao; Ying Yang; Hui Yu; Wensheng Yu; Xiangting Dong (Journal of Environmental Chemical Engineering, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Artificial intelligence and real-world data for drug and food safety – A regulatory science perspective - Shraddha Thakkar; William Slikker; Frank Yiannas; Primal Silva; Burton Blais; Kern Rei Chng; Zhichao Liu; Alok Adholeya; Francesco Pappalardo; Mônica da Luz Carvalho Soares; Patrick E. Beeler; Maurice Whelan; et al. (Regulatory Toxicology and Pharmacology, 2023)

A simple and efficient protocol for transient transformation of sliced grape berries - Mao-Song Pei; Hai-Nan Liu; Charles Ampomah-Dwamena; Tong-Lu Wei; Yi-He Yu; Jia-Bing Jiao; Ying-Ying Lv; Feng Li; Hong-Chao Li; Xue-Jie Zhu; Da-Long Guo (Protoplasma, 2023)

Chemical constituents and biological activities of Artemisia argyi H.Lév. & vaniot - Yun-hong Zhang; Zhu-tao Shao; Guang-ming Bi; Yi-wei Sun; Yu-meng Wang; Da-li Meng (Natural Product Research, 2023)

Triterpenoids from the leaves of Abies koreana and their biological activities - Dong Jun Lee; Seong-Min Hong; Da Hye Yoon; Song Lim Ham; Jonghwan Kim; Sun Yeou Kim; Sang Un Choi; Chung Sub Kim; Kang Ro Lee (Phytochemistry, 2023)

Effects of dietary glycerol supplementation on meat quality, palatability, and lipid metabolism gene expression in the longissimus thoracis of Hanwoo steers - Dilla Mareistia Fassah; Hyeok Joong Kang; Seok-Hyeon Beak; Da Jin Sol Jung; Inhyuk Jeong; Sang Weon Na; Seon Pil Yoo; Soo Jong Hong; Hyun Jin Kim; Md. Najmul Haque; Hyun Jung Lee; Cheorun Jo; et al. (Meat Science, 2023)

Oleuropein induces apoptosis in colorectal tumor spheres via mitochondrial fission - Da Yeon Kim; Sangmi Park; Jisoo Yun; Woongbi Jang; Vinoth Kumar Rethineswaran; Le Thi Hong Van; Ly Thanh Truong Giang; Jaewoo Choi; Hye ji Lim; Sang-Mo Kwon (Molecular & Cellular Toxicology, 2023)

Gestational exposure to organophosphate esters and adiposity measures of children up to 6 years: Effect modification by breastfeeding - Yafei Chen; Xiaohua Zhang; Ziliang Wang; Zhengwei Yuan; Min Luan; Wei Yuan; Hong Liang; Hexia Chen; Da Chen; Yan Yang; Maohua Miao (International Journal of Hygiene and Environmental Health, 2023)

Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat - Yang Liu; Chun-Li Qi; Da-Wei Li; Hong-Ye Li; Rui-Man Li; Wei-Dong Yang (Food and Chemical Toxicology, 2023)

Bio-mineralized tin/bismuth oxide nanoparticles with silk fibroins for efficient electrochemical detection of 2-nitroaniline in river water samples - Subash Vetri Selvi; Adhimoorthy Prasannan; Hao Yu; Varghese Lincy; Po-Da Hong (Environmental Research, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Pseudomonas citri sp. nov., a potential novel plant growth promoting bacterium isolated from rhizosphere soil of citrus - Hong Gao; Guang-Da Feng; Zengwei Feng; Qing Yao; Jiali Li; Xiaoqin Deng; Xiaoran Li; Honghui Zhu (Antonie van Leeuwenhoek, 2023)

Molecular mechanism of di-n-butyl phthalate promotion of bladder cancer development - En-Hui Li; Bai-Hui Xu; Hai-Bin Wei; Yu-Chen Bai; Qi Zhang; Wei-Wen Yu; Zhi-Hui Xu; Xiao-Long Qi; Da-Hong Zhang; Heng Wang (Toxicology in Vitro, 2023)

Deconstruction of pineapple peel cellulose based on Fe2+ assisted cold plasma pretreatment for cellulose nanofibrils preparation - Hong Zhu; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Chemistry, 2023)

Melatonin improves the removal and the reduction of Cr(VI) and alleviates the chromium toxicity by antioxidative machinery in Rhodobacter sphaeroides - Hao-Tian Mao; Lun-Xing Chen; Meng-Ying Zhang; Qiu-Yun Shi; Hong Xu; Da-Yan Zhang; Zhong-Wei Zhang; Ming Yuan; Shu Yuan; Huai-Yu Zhang; Yan-Qiu Su; Yang-Er Chen (Environmental Pollution, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Prenatal exposure to organophosphate esters is associated with decreased anogenital distance in offspring - Min Luan; Hong Liang; Yafei Chen; Da Chen; Honglei Ji; Hexia Chen; Maohua Miao; Wei Yuan (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Exploring plant growth promoting rhizobacteria potential for green agriculture system to optimize sweet potato productivity and soil sustainability in northern Jiangsu, China - Yi-Yang Yu; Jing-Da Xu; Mei-Zhen Gao; Tao-Xiang Huang; Ying Zheng; Yi-Yuan Zhang; Yun-Peng Wang; Yu-Ming Luo; Ying Zhang; Yong-Hong Hu; Jian-Hua Guo; Chun-Hao Jiang (European Journal of Agronomy, 2023)

Regulation of reactive oxygen species on production, release, and early germination of archeospores in Pyropia yezoensis - Chao-Feng Teng; Da-Hai Gao; Hong-Chang Ding; Xing-Hong Yan (Algal Research, 2023)

Local and remote forcing on the interannual variations of the sedimentary δ15N in Santa Barbara Basin during the past 80 years - Hanyue Xu; Da-Wei Li; Hong-Chun Li; Meixun Zhao; William M. Berelson; Gui’e Jin; Li Li; Satabdi Misra (Frontiers in Marine Science, 2022)
Sedimentary nitrogen isotope (δ 15 N sed ) in Santa Barbara Basin (SBB) has been mostly interpreted as the record of the eastern tropical North Pacific (ETNP) intermediate water denitrification process. Nevertheless, debate remains regarding sources and control mechanisms of δ 15 N sed signal in SBB. Multi-proxy analyses including δ 15 N sed , total organic carbon (TOC), total nitrogen (TN), C/N ratio, and marine biomarkers were performed on a 46-cm sediment core (SBB-190629) collected from SBB in 2019. The core was dated with varve counting and 210 Pb dating method, showing a depositional history of 1938–2019 CE with a sedimentation rate of 0.564 cm/year. The findings show that the δ 15 N sed record (at ~0.25-year resolution) ranges from 6.24‰ to 7.43‰, which was affected by both local and remote forcing. The long-term variations of the SBB δ 15 N sed signature show a general decreasing trend from 1940 to the late 1980s, low values during 1980~2000, and an increase afterward, which is thought to reflect changes in ETNP denitrification induced by the strength of tropical trade winds. Our results also reveal a series of abrupt annual to multiannual changes, superimposed on the long-term variation mentioned above. The SBB local δ 15 N signal (Δδ 15 N SBB ) is accessed by using the deviation from the mean δ 15 N (Δδ 15 N) of SBB-190629 to subtract the Δδ 15 N of the ETNP. The Δδ 15 N SBB record compares well with redox-sensitive proxies (Re/Mo ratio and C 29 stanol/stenol ratio) from the SBB bottom water and with the OC marine content calculated based on the C/N ratio mixing model, indicating that the Δδ 15 N SBB is mainly controlled by bottom water denitrification, which was induced by the change of upwelling intensity and marine productivity. Since various climatic factors (e.g., El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), and North Pacific Gyre Oscillation (NPGO)) have different impacts on the upwelling intensity (hence the marine productivity and denitrification) in SBB on different timescales, the influence of combined climatic factors on SBB denitrification is time dependent.

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Chemical and genomic analyses of a marine-derived Streptomyces sp. V17-9 producing amino acid derivatives and siderophores - Da-Eun Kim; Sung-Chul Hong; Yoonyong Yang; Jaeyoung Choi; Jin-Soo Park (Frontiers in Marine Science, 2022)
Streptomyces , the largest genus in Actinobacteria, has been known as a chemically prolific bacterial group producing pharmaceutically important small molecules. Various endeavors have been made to discover novel secondary metabolites from strains inhabiting diverse environmental niches. In our course of collecting bacterial strains to discover biologically active molecules, a marine-derived Streptomyces sp. V17-9 was isolated from a seagrass collected from a beach on Côn Đảo, Vietnam. Phylogenetic and genomic analyses suggested the possibility that this strain might form a new taxonomic group with a few closely related unclassified strains. The genome sequence of strain V17-9 was predicted to have 20 putative biosynthetic gene clusters. A chemical investigation identified amino acid derivatives ( N -acetyltryptamine, N -acetyltyramine, and 6-prenyltryptophol) and siderophores (desferrioxamine E and spoxazomicin A) from culture extracts, linking gene clusters with actual productions. In particular, prenylated indole compounds were enhanced in production as part of metabolic conversion under supplement with ferric ions. Sequence similarity networks for indole and siderophore gene clusters showed their diversity and complexity in the genus Streptomyces . Phylogenomic analysis of gene cluster for 6-prenyltryptophol suggested strains of genomic potential for production of such compounds. They also suggested how these gene clusters may have shaped the biosynthesis of natural products. Chemotaxonomic profiling coupled with genome analysis would provide new insights into comparative studies on Actinobacteria producing prenylated indoles and siderophores.

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Study on the formation of gangue wall and the stress distribution of surrounding rock in gob side entry with roof cutting - Guo Peng-fei; Lian Hong-da; Ye Keng-keng; Tao Zhi-gang; Yuan Ya-di; Zhen En-ze (Arabian Journal of Geosciences, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Different Surface Appearances Caused by Unbalanced Mn2+ Accumulation in Gallstones Consisting of Cholesterol and CaCO3 Obtained from a Patient After Cholecystectomy - Da-Yong Lu; Jin Zhang; Qiao-Li Liu; Hong-Guang Wang; Meng Cui (Biological Trace Element Research, 2022)

Magnetotactic bacteria in vertical sediments of volcanic lakes in NE China appear Alphaproteobacteria dominated distribution regardless of waterbody types - Tao Liu; Huiyun Da; Shuang Zhang; Weidong Wang; Hong Pan; Lei Yan (World Journal of Microbiology and Biotechnology, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Dissecting the Neural Circuitry for Pain Modulation and Chronic Pain: Insights from Optogenetics - Fang Guo; Yu Du; Feng-Hui Qu; Shi-Da Lin; Zhong Chen; Shi-Hong Zhang (Neuroscience Bulletin, 2022)
Pain is an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage. The processing of pain involves complicated modulation at the levels of the periphery, spinal cord, and brain. The pathogenesis of chronic pain is still not fully understood, which makes the clinical treatment challenging. Optogenetics, which combines optical and genetic technologies, can precisely intervene in the activity of specific groups of neurons and elements of the related circuits. Taking advantage of optogenetics, researchers have achieved a body of new findings that shed light on the cellular and circuit mechanisms of pain transmission, pain modulation, and chronic pain both in the periphery and the central nervous system. In this review, we summarize recent findings in pain research using optogenetic approaches and discuss their significance in understanding the pathogenesis of chronic pain.

Identification and expression profiling of HSP20 genes in Neoporphyra haitanensis - Ling-Na Peng; Lin-Bin Huang; Tian-Yu Gui; Da-Hai Gao; Xing-Hong Yan (Journal of Applied Phycology, 2022)

Multi-omics analysis reveals metabolism of okadaic acid in gut lumen of rat - Yang Liu; Yang Lu; Yu-Hu Jiao; Da-Wei Li; Hong-Ye Li; Wei-Dong Yang (Archives of Toxicology, 2022)

Effect of Chromium Supplementation on Blood Glucose and Lipid Levels in Patients with Type 2 Diabetes Mellitus: a Systematic Review and Meta-analysis - Fengyi Zhao; Da Pan; Niannian Wang; Hui Xia; Hong Zhang; Shaokang Wang; Guiju Sun (Biological Trace Element Research, 2022)

Unsubstituted and Methylated PAHs in Surface Sediment of Urban Rivers in the Red River Delta (Hanoi, Vietnam): Concentrations, Profiles, Sources, and Ecological Risk Assessment - Anh Quoc Hoang; Shin Takahashi; Nhu Da Le; Thi Thu Ha Hoang; Thi Thuy Duong; Thi Mai Huong Pham; Tien Dat Nguyen; Thi Xuan Binh Phung; Thi Anh Huong Nguyen; Huu Tuyen Le; Minh Tue Nguyen; Minh Binh Tu; et al. (Bulletin of Environmental Contamination and Toxicology, 2021)

Psychological and occupational impact on healthcare workers and its associated factors during the COVID-19 outbreak in China - Xiaodan Zhang; Ye Jiang; Hu Yu; Yafen Jiang; Qiongfeng Guan; Weihe Zhao; Yingying Mao; Danfeng Huang; Wenke Hong; Da Li (International Archives of Occupational and Environmental Health, 2021)

Safety evaluation and ibuprofen removal via an Alternanthera philoxeroides-based biochar - Yuan-da Du; Xin-qian Zhang; Li Shu; Yu Feng; Cui Lv; Hong-qiang Liu; Fei Xu; Qian Wang; Cong-cong Zhao; Qiang Kong (Environmental Science and Pollution Research, 2021)

Effects of Copper Supplementation on Blood Lipid Level: a Systematic Review and a Meta-Analysis on Randomized Clinical Trials - Shaokang Wang; Niannian Wang; Da Pan; Hong Zhang; Guiju Sun (Biological Trace Element Research, 2021)

Neuroprotective triterpene saponins from the leaves of Panax notoginseng - Ji-Wu Huang; Yi-Qian Du; Chuang-Jun Li; Jing-Zhi Yang; Jie Ma; Ying-Da Zang; Nai-Hong Chen; Dong-Ming Zhang (Natural Product Research, 2021)

Study on the correlation of bisphenol A exposure, pro-inflammatory gene expression, and C-reactive protein with potential cardiovascular disease symptoms in young adults - Chao-Ming Tsen; Jia-Hong Liu; Da-Peng Yang; How-Ran Chao; Jyh-Larng Chen; Wei-Chun Chou; Yi-Chen Ho; Chun-Yu Chuang (Environmental Science and Pollution Research, 2021)

Incineration experiment of medical waste of novel coronavirus pneumonia (COVID-19) in a mobile animal carcass incinerator - Shaorui Zhang; Yanjun Zhang; Fengjun Wang; Da Kang; Jingjie Wang; Minghao Wang; Chunwei Zhang; Yongtang Wang; Hong Liu; Baodong Zhou; Yong Wu (Waste Disposal & Sustainable Energy, 2021)

Modeling Wave Propagation in Rock Masses Using the Contact Potential-Based Three-Dimensional Discontinuous Deformation Analysis Method - Yongtao Yang; Dongdong Xu; Hong Zheng; Zhijun Wu; Da Huang (Rock Mechanics and Rock Engineering, 2021)

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Metagenomic and 14 C tracing evidence for autotrophic microbial CO 2 fixation in paddy soils - Ke‐Qing Xiao; Ti‐Da Ge; Xiao‐Hong Wu; Caroline L. Peacock; Zhen‐Ke Zhu; Jingjing Peng; Peng Bao; Jin‐Shui Wu; Yong‐Guan Zhu (Environmental Microbiology, 2021)
Summary Autotrophic carbon dioxide (CO 2 ) fixation by microbes is ubiquitous in the environment and potentially contributes to the soil organic carbon (SOC) pool. However, the multiple autotrophic pathways of microbial carbon assimilation and fixation in paddy soils remain poorly characterized. In this study, we combine metagenomic analysis with 14 C‐labelling to investigate all known autotrophic pathways and CO 2 assimilation mechanisms in five typical paddy soils from southern China. Marker genes of six autotrophic pathways are detected in all soil samples, which are dominated by the cbbL genes (67%–82%) coding the ribulose‐bisphosphate carboxylase large chain in the Calvin cycle. These marker genes are associated with a broad range of phototrophic and chemotrophic genera. Significant amounts of 14 C‐CO 2 are assimilated into SOC (74.3–175.8 mg 14 C kg −1 ) and microbial biomass (5.2–24.1 mg 14 C kg −1 ) after 45 days incubation, where more than 70% of 14 C‐SOC was concentrated in the relatively stable humin fractions. These results show that paddy soil microbes contain the genetic potential for autotrophic carbon fixation spreading over broad taxonomic ranges, and can incorporate atmospheric carbon into organic components, which ultimately contribute to the stable SOC pool.

Synthesis, Crystal Structures, Fluorescence and Quantum Chemical Investigations of some Multi-Substituted Quinoline Derivatives - Thi Hong Hai Le; Thi Ngoc Vinh Nguyen; Tuan Cuong Ngo; Van Co Le; Thi Yen Hang Bui; Thi Da Tran; Huu Dinh Nguyen; Luc Van Meervelt (Journal of Fluorescence, 2021)

The Complete Genome Sequence of a Bacterial Strain with High Alkalic Xylanase Activity Isolated from the Sludge Near a Papermill - Si Chen; Hao Feng; Xin Li; Hong-jun Chao; Jing Wu; Jun Liu; Wen-jun Zhu; Da-zhong Yan (Current Microbiology, 2020)

Genome-wide investigation of a Korean synthetic breed, Woori-Heukdon using the Illumina PorcineSNP60K BeadChip - Yong-Min Kim; Ha-Seung Seong; Jung-Jae Lee; Da-Hye Son; Jin-Su Kim; Soo-Jin Sa; Young-Sin Kim; Tae-Jeong Choi; Kyu-Ho Cho; Joon-Ki Hong; Jung-Woo Choi; Eun-Seok Cho (Genes & Genomics, 2020)

Inhibition of orf virus replication in goat skin fibroblast cells by the HSPA1B protein, as demonstrated by iTRAQ-based quantitative proteome analysis - Jun-hong Hao; Han-jin Kong; Ming-hao Yan; Chao-chao Shen; Guo-wei Xu; Da-jun Zhang; Ke-shan Zhang; Hai-xue Zheng; Xiang-tao Liu (Archives of Virology, 2020)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Engineered M13 Peptide Carrier Promotes Angiogenic Potential of Patient-Derived Human Cardiac Progenitor Cells and In Vivo Engraftment - Woong Bi Jang; Seung Taek Ji; Ji Hye Park; Yeon-Ju Kim; Songhwa Kang; Da Yeon Kim; Na-Kyung Lee; Jin Su Kim; Hye Ji Lim; Jaewoo Choi; Thi Hong Van Le; Thanh Truong Giang Ly; et al. (Tissue Engineering and Regenerative Medicine, 2020)

Triterpenoid saponins with hepatoprotective effects from the fresh leaves of Metapanax delavayi - Xin Wei; Da-Fang Gao; Yuko Abe; Yoshihisa Tanaka; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Seasonal Variation of Lipid Profile of Oyster Crassostrea talienwhanensis from the Yellow Sea Area - Yan-Fei Liu; Zi-Xuan Wu; Jing Zhang; Yu-Xin Liu; Zhong-Yuan Liu; Hong-Kai Xie; Kanyasiri Rakariyatham; Da-Yong Zhou (Journal of Aquatic Food Product Technology, 2020)

Ultrasonography-Based Qualitative and Quantitative Evaluation Approaches for Pompe Disease - Yueh-Hui Lee; Hong-Jen Chiou; Da-Tian Bau; Dau-Ming Niu; Ting-Rong Hsu; Hsuan-En Huang; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to propose the qualitative and quantitative approaches to evaluate the skeletal muscle ultrasound images of 23 Pompe disease (i.e., acid maltase deficiency, AMD) patients and 14 normal subjects. Methods A cohort of 23 AMD patients and 14 normal subjects has been investigated. We compared the B-mode echo intensity of the rectus femoris muscle with that of its surrounding fat (subcutaneous fat) and proposed a qualitative grading method. Quantitative analysis of the region of interest (ROI) with the echo intensity and the segmented area was also performed. Results Qualitative results showed that AMD patients without clinical symptoms (without undergoing ERT) had the highest distribution of Grade 1, and AMD patients undergoing ERT had the widest distribution of Grade 2, and control group (n = 14) with the highest distribution of Grade 1. Using the segmented area approach, quantitative results showed that AMD patients undergoing ERT had the largest and widest distribution. Meanwhile the control subjects (normal subjects) had the lowest and the narrowest areas. The echo intensity of the segmented ROI of AMD patients undergoing ERT displayed the highest and widest (inhomogeneous) distributions. By contrast, the echo intensity of AMD patients without clinical symptoms was slightly increased and with low inhomogeneity. Conclusion The proposed ultrasonography-based qualitative and quantitative approach may be used to evaluate the severity of muscle destruction for AMD patients. Besides, the quantitative segmented area with regression analysis could help predict the incidence of onset of Pompe disease patients.

Plastidial and ER Triacylglycerol Biosynthesis in a Growth Phase-Dependent Manner in the Heterokont Nannochloropsis oceanica - Dan Huang; Da-Wei Li; Srinivasan Balamurugan; Jian-Wei Zheng; Wan-Jun Liu; Li-Gong Zou; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Frontiers in Marine Science, 2020)

Ultrastructure analysis of white spot syndrome virus (WSSV) - Li Li; Yongcong Hong; Da Huo; Pumo Cai (Archives of Virology, 2020)

The efflux pump inhibitor tetrandrine exhibits synergism with fluconazole or voriconazole against Candida parapsilosis - Ya-Jing Zhao; Wei-Da Liu; Yong-Nian Shen; Dong-Mei Li; Kun-Ju Zhu; Hong Zhang (Molecular Biology Reports, 2019)

A review of computational algorithms for CpG islands detection - Rana Adnan Tahir; Da Zheng; Amina Nazir; Hong Qing (Journal of Biosciences, 2019)

A critical review on environmental implications, recycling strategies, and ecological remediation for mine tailings - Da-Mao Xu; Chang-Lin Zhan; Hong-Xia Liu; Han-Zhi Lin (Environmental Science and Pollution Research, 2019)

Complete Genome Sequence of a Chlorobenzene Degrader, Pandoraea pnomenusa MCB032 - Hong-Jun Chao; Yuan-yuan Chen; Jing Wu; Da-Zhong Yan; Ning-Yi Zhou (Current Microbiology, 2019)

Glacier change in the Tanggula Mountains, Tibetan Plateau, in 1969–2015 - Hong-yu Duan; Xiao-jun Yao; Shi-yin Liu; Yong-peng Gao; Miao-miao Qi; Juan Liu; Da-hong Zhang; Xiao-feng Li (Journal of Mountain Science, 2019)

Fraction distribution of arsenic in different-sized atmospheric particulate matters - Jiao-Jiao Xie; Chun-Gang Yuan; Jin Xie; Yi-Wen Shen; Da-Wen Zha; Ke-Gang Zhang; Hong-Tao Zhu (Environmental Science and Pollution Research, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

A geostatistic investigation of the comprehensive evaluation of fertility and spatial heterogeneity of forest soil nutrients in hilly and mountainous regions of southern China - Da-ping Song; Hong Li; Shan-jiang Liu; Guo-yuan Zou; Dong-sheng Liu (Arabian Journal of Geosciences, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Several environmental endocrine disruptors in beverages from South China: occurrence and human exposure - Hong Wu; Liu-Hong Wu; Fei Wang; Chong-Jing Gao; Da Chen; Ying Guo (Environmental Science and Pollution Research, 2019)

Systematic study of the quality and safety of chilled pork from wet markets, supermarkets, and online markets in China - Dong-wen Hu; Chen-xing Liu; Hong-bo Zhao; Da-xi Ren; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Depositional sequence response to Paleogene Lake level and Paleoclimate changes in the northern Liaoxi depression, eastern China - Nanan Gao; Changsong Lin; Da Gao; Hong Li (Arabian Journal of Geosciences, 2018)

Constitutive and Chloroplast Targeted Expression of Acetyl-CoA Carboxylase in Oleaginous Microalgae Elevates Fatty Acid Biosynthesis - Da-Wei Li; Wei-Hong Xie; Ting-Bin Hao; Jia-Xi Cai; Tian-Bao Zhou; Srinivasan Balamurugan; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Marine Biotechnology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Sevoflurane Affects Oxidative Stress and Alters Apoptosis Status in Children and Cultured Neural Stem Cells - Xue Zhou; Dihan Lu; Wen-da Li; Xiao-hui Chen; Xiao-yu Yang; Xi Chen; Zhi-bin Zhou; Jiang-Hong Ye; Xia Feng (Neurotoxicity Research, 2018)

Molecular characterization of a putative gammapartitivirus in the phytopathogenic fungus Nigrospora oryzae - Jin Xiu Yu; Jun Zi Zhu; Ying Wang; Chao Jun Zhang; Jie Zhong; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Archives of Virology, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

M-type thioredoxins are involved in the xanthophyll cycle and proton motive force to alter NPQ under low-light conditions in Arabidopsis - Qingen Da; Ting Sun; Menglong Wang; Honglei Jin; Mengshu Li; Dongru Feng; Jinfa Wang; Hong-Bin Wang; Bing Liu (Plant Cell Reports, 2018)

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Domain of Unknown Function 143 is required for the functioning of PEP-associated protein DG238 in the chloroplast - Menglong Wang; Lan Jiang; Qingen Da; Jun Liu; Dongru Feng; Jinfa Wang; Hong-Bin Wang; Hong-Lei Jin (Journal of Plant Biology, 2017)

Evaluating the effectiveness of a novel atomized liquid needle-free transdermal delivery system - Yi-Huei Huang; Chieh-Shen Hu; Yi-Jhen Ke; Chiao-Hsi Chiang; Po-Da Hong; Ming-Kung Yeh (Drug Delivery and Translational Research, 2017)

A mitovirus isolated from the phytopathogenic fungus Alternaria brassicicola - Yi Chen; Hong Hong Shang; Hong Qi Yang; Bi Da Gao; Jie Zhong (Archives of Virology, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Occurrence and risk assessment of phthalate esters (PAEs) in agricultural soils of the Sanjiang Plain, northeast China - He Wang; Hong Liang; Da-Wen Gao (Environmental Science and Pollution Research, 2017)

Analysis on shear wave velocity structure of a gravel landslide based on dual-source surface wave method - Xing-qian Xu; Li-jun Su; Guang-da Zhang; Hong-hu Zhu (Landslides, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Non-Destructive and rapid evaluation of staple foods quality by using spectroscopic techniques: A review - Wen-Hao Su; Hong-Ju He; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

A novel fusarivirus isolated from the phytopathogenic fungus Nigrospora oryzae - Jie Zhong; Si Qi Zhao; Gui Fang Li; Xi Dan Pang; Xiao Jun Deng; Hong Jian Zhu; Bi Da Gao; Qian Zhou (Virus Genes, 2016)

Elliptic Shape Prior Dynamic Programming for Accurate Vessel Segmentation in MRI Sequences with Automated Optimal Parameter Selection - Da-Chuan Cheng; Sin-Kuo Chai; Shi-Rong Xu; Shing-Hong Liu (Journal of Medical and Biological Engineering, 2016)

Molecular epidemiology and phylogenetic analysis of HA gene of influenza A(H1N1)pdm09 strain during 2010–2014 in Dalian, North China - Yan Han; Nan Sun; Qiu-yue Lv; Dan-hong Liu; Da-peng Liu (Virus Genes, 2016)

ECV304/C6 coculture model of the BBB coupled with LC–MS analysis for drug screening from Rhubarb extract - Jiang-Feng Yuan; Hui-Hui Ji; Zhi-Jun Qiu; Da-Hong Wang (Medicinal Chemistry Research, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Cytotoxic monoterpenoid indole alkaloids isolated from the barks of Voacanga africana Staph. - Hong-Mei Chen; Yu-Ting Yang; Hong-Xiang Li; Zhi-Xing Cao; Xiao-Mei Dan; Ling Mei; Da-Le Guo; Chuan-Xia Song; Yu Dai; Jia Hu; Yun Deng (Natural Product Research, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Changes in the activities of starch metabolism enzymes in rice grains in response to elevated CO2 concentration - Li-Yong Xie; Er-Da Lin; Hong-Liang Zhao; Yong-Xiang Feng (International Journal of Biometeorology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

MdSOS2L1 phosphorylates MdVHA-B1 to modulate malate accumulation in response to salinity in apple - Da-Gang Hu; Cui-Hui Sun; Mei-Hong Sun; Yu-Jin Hao (Plant Cell Reports, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A novel single-stranded RNA virus isolated from the rice-pathogenic fungus Magnaporthe oryzae with similarity to members of the family Tombusviridae - Ye-Ping Ai; Jie Zhong; Chuan-Yuan Chen; Hong-Jian Zhu; Bi-Da Gao (Archives of Virology, 2016)

Potential natural exposure of endangered red-crowned crane (Grus japonensis) to mycotoxins aflatoxin B1, deoxynivalenol, zearalenone, T-2 toxin, and ochratoxin A - Da-wei Liu; Hong-yi Liu; Hai-bin Zhang; Ming-chang Cao; Yong Sun; Wen-da Wu; Chang-hu Lu (Journal of Zhejiang University-SCIENCE B, 2016)

Molecular identification of a novel victorivirus from the phytopathogenic fungus Nigrospora oryzae - Jie Zhong; Qian Zhou; Yue Hu; Hong Jian Zhu; Bi Da Gao (Virus Genes, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Applications of Computer Vision for Assessing Quality of Agri-food Products: A Review of Recent Research Advances - Ji Ma; Da-Wen Sun; Jia-Huan Qu; Dan Liu; Hongbin Pu; Wen-Hong Gao; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Identification and characterization of eighteen polymorphic microsatellite loci for a threatened freshwater fish, Botia superciliaris - FEI XIONG; HONG-YAN LIU; XIN-BIN DUAN; DA-QING CHEN (Journal of Genetics, 2015)

Multiple glacial refugia for cool‐temperate deciduous trees in northern East Asia: the Mongolian oak as a case study - Yan‐Fei Zeng; Wen‐Ting Wang; Wan‐Jin Liao; Hong‐Fang Wang; Da‐Yong Zhang (Molecular Ecology, 2015)
In East Asia, temperate forests are predicted to have retracted southward to c . 30° N during the last glacial maximum ( LGM ) based on fossil pollen data, whereas phylogeographic studies have often suggested glacial in situ survival of cool‐temperate deciduous trees in their modern northern ranges. Here we report a study of the genetic diversity and structure of 29 natural Mongolian oak ( Quercus mongolica ) populations using 19 nuclear simple sequence repeat ( nSSR ) loci and four chloroplast DNA fragments. Bayesian clustering analysis with nSSR s revealed five groups, which were inferred by approximate Bayesian computation ( ABC ) to have diverged in multiple refugia through multiple glacial–interglacial cycles. Analysis of chloroplast DNA variation revealed four lineages that were largely but incompletely geographically disjunct. Ecological niche modelling (ENMs) indicated a southward range shift of the oak's distribution at the LGM , although high suitability scores were also evident in the Changbai Mts. (Northeast China), the Korean Peninsula, areas surrounding the Bohai Sea, and along the coast of the Russian Far East. In addition, endemic chloroplast DNA haplotypes and nuclear lineages occurred in high‐latitude northern areas where the ENM predicted no suitable habitat. The combined evidence from nuclear and chloroplast DNA , and the results of the ENM clearly demonstrate that multiple northern refugia, including cryptic ones, were maintained across the current distributional range of the Mongolian oak during the LGM or earlier glacial periods. Though spatially limited, postglacial expansions from these refugia have led to a pattern of decreased genetic diversity with increasing latitude.

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Protective effect of low dose gadolinium chloride against isoproterenol-induced myocardial injury in rat - Yuan-Yuan Zheng; Hai-Hong Zhang; Xin-Xin Yan; Min Chen; Tian-Yu Qi; Lan-E Zhang; Da-Li Luo (Apoptosis, 2015)

Angiopoietin-like protein 2 may mediate the inflammation in murine mastitis through the activation of interleukin-6 and tumour necrosis factor-α - Ji-Ying Wang; Hong-Bo Xiao; Zhi-Liang Sun; Da-Sheng Zhang (World Journal of Microbiology and Biotechnology, 2015)

PPARα Agonist Fenofibrate Ameliorates Learning and Memory Deficits in Rats Following Global Cerebral Ischemia - Ai-Guo Xuan; Yan Chen; Da-Hong Long; Meng Zhang; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Xiao-Song He; Wen-Liang Chen (Molecular Neurobiology, 2015)

A novel mycovirus identified from the rice false smut fungus Ustilaginoidea virens - Hong Jian Zhu; Dan Chen; Jie Zhong; Shuai Yang Zhang; Bi Da Gao (Virus Genes, 2015)

Genome sequence of a novel endornavirus from the phytopathogenic fungus Alternaria brassicicola - Hong-Hong Shang; Jie Zhong; Ru-Jia Zhang; Chuan-Yuan Chen; Bi-Da Gao; Hong-Jian Zhu (Archives of Virology, 2015)

The complete nucleotide sequence and genomic organization of a novel victorivirus with two non-overlapping ORFs, identified in the plant-pathogenic fungus Phomopsis vexans - Ru Jia Zhang; Jie Zhong; Hong Hong Shang; Xian Ting Pan; Hong Jian Zhu; Bi Da Gao (Archives of Virology, 2015)

Actinomadura amylolytica sp. nov. and Actinomadura cellulosilytica sp. nov., isolated from geothermally heated soil - Jian-Yu Jiao; Lan Liu; En-Min Zhou; Da-Qiao Wei; Hong Ming; Wen-Dong Xian; Chang-Guo Yuan; Jing-Mei Zhong; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Low-frequency data analysis and expansion - Jun-Hua Zhang; Bin-Bin Zhang; Zai-Jin Zhang; Hong-Xian Liang; Da-Ming Ge (Applied Geophysics, 2015)

Nondestructive Spectroscopic and Imaging Techniques for Quality Evaluation and Assessment of Fish and Fish Products - Hong-Ju He; Di Wu; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2015)

Docetaxel Modulates the Delayed Rectifier Potassium Current (I K) and ATP-Sensitive Potassium Current (I KATP) in Human Breast Cancer Cells - Tao Sun; Zhi-Guo Song; Da-Qing Jiang; Hong-Guang Nie; Dong-Yun Han (The Journal of Membrane Biology, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Valproic Acid Alleviates Memory Deficits and Attenuates Amyloid-β Deposition in Transgenic Mouse Model of Alzheimer’s Disease - Ai-Guo Xuan; Xue-Bing Pan; Peng Wei; Wei-Dong Ji; Wen-Juan Zhang; Ji-Hong Liu; Le-Peng Hong; Wen-Liang Chen; Da-Hong Long (Molecular Neurobiology, 2015)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Synthesis and evaluation of anticonvulsant and antidepressant activities of 7-alkyl-7H-tetrazolo[1,5-g]purine derivatives - Shi-Ben Wang; Xian-Qing Deng; Da-Chuan Liu; Hong-Jian Zhang; Zhe-Shan Quan (Medicinal Chemistry Research, 2014)

Construction of Novel Chloroplast Expression Vector and Development of an Efficient Transformation System for the Diatom Phaeodactylum tricornutum - Wei-Hong Xie; Cong-Cong Zhu; Nai-Sheng Zhang; Da-Wei Li; Wei-Dong Yang; Jie-Sheng Liu; Ramalingam Sathishkumar; Hong-Ye Li (Marine Biotechnology, 2014)

Effects of heating conditions on fatty acids and volatile compounds in foot muscle of abalone Haliotis discus hannai Ino - Hong-Xu Wang; Lei Qin; Yan Wang; Da-Yong Zhou; Shuang Song; Xu-Song Wang; Bei-Wei Zhu (Fisheries Science, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Dynamics of ruderal species diversity under the rapid urbanization over the past half century in Harbin, Northeast China - Xiaoshuang Chen; Weibo Wang; Hong Liang; Xiaoli Liu; Liangjun Da (Urban Ecosystems, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Complete genome sequence and organization of a novel virus from the rice false smut fungus Ustilaginoidea virens - Jie Zhong; Jun-Zi Zhu; Xiang-Hua Lei; Dan Chen; Hong-Jian Zhu; Bi-Da Gao (Virus Genes, 2014)

Construction, characterization and expression of full length cDNA clone of sheep YAP1 gene - Wei Sun; Da Li; Rui Su; Hassan H. Musa; Ling Chen; Hong Zhou (Molecular Biology Reports, 2014)

Socio-demographic and clinical characteristics of heavy and non-heavy smokers among schizophrenia inpatients in a Chinese Han population - Xiang Yang Zhang; Da Chun Chen; Yun Long Tan; Mei Hong Xiu; Jingyi Cui; Li Hui; Fu De Yang; Thomas R Kosten (Psychopharmacology, 2014)

Effect of Intravenous Infusion of Dexmedetomidine Combined with Inhalation of Isoflurane on Arterial Oxygenation and Intrapulmonary Shunt During Single-Lung Ventilation - Rui Xia; Hong Yin; Zhong-yuan Xia; Qing-jun Mao; Gong-da Chen; Wei Xu (Cell Biochemistry and Biophysics, 2013)

Porous-grain-upper-boundary model and its application to Tarim Basin carbonates - Yu-Qian Guo; Hong-Da Ma; Kai-Bo Shi; Hong Cao; Lu-Zhong Huang; Feng-Chang Yao; Tian-Yue Hu (Applied Geophysics, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Immunologic Mechanism of Patchouli Alcohol Anti-H1N1 Influenza Virus May Through Regulation of the RLH Signal Pathway In Vitro - Xian-Lin Wu; Da-Hong Ju; Jia Chen; Bin Yu; Kang-Li Liu; Jin-Xiong He; Cong-Qi Dai; Sha Wu; Zhou Chang; You-Ping Wang; Xiao-Yin Chen (Current Microbiology, 2013)

Study on the In Vitro Effects of the Mixtures of Polycyclic Aromatic Hydrocarbons (PAHs) and Heavy Metals on Ethoxyresorufin-O-Deethylase (EROD) Activity in Mossambica tilapia Liver - Da Xiong Han; Hai Yan Wang; Hong Wei Yue; Su Min Wang (Bulletin of Environmental Contamination and Toxicology, 2013)

The First Case of Phaeohyphomycosis Caused by Rhinocladiella basitona in an Immunocompetent Child in China - Qing Cai; Gui-Xia Lv; Yi-Qun Jiang; Huan Mei; Su-Quan Hu; Hong-Bin Xu; Xin-Feng Wu; Yong-Nian Shen; Wei-Da Liu (Mycopathologia, 2013)

In vitro interactions between rat bone marrow-derived endothelial progenitor cells and hepatic stellate cells - Feng Liu; Zhi-da Liu; Nan Wu; Jiang-Hua Wang; Heng-Hui Zhang; Ran Fei; Xu Cong; Hong-song Chen; Lai Wei (In Vitro Cellular & Developmental Biology - Animal, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

Auto- and Cross-repression of Three Arabidopsis WRKY Transcription Factors WRKY18, WRKY40, and WRKY60 Negatively Involved in ABA Signaling - Lu Yan; Zhi-Qiang Liu; Yan-Hong Xu; Kai Lu; Xiao-Fang Wang; Da-Peng Zhang (Journal of Plant Growth Regulation, 2013)

Development of microsatellite markers for Leptobotia rubrilaris, a threatened fish species in the Yangtze River - Xin Bin Duan; Hong Yan Liu; Fei Xiong; Da Qing Chen (Conservation Genetics Resources, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Expression of HOXD3 correlates with shorter survival in patients with invasive breast cancer - Cheng Shaoqiang; Zhang Yue; Liu Yang; Zhao Hong; Zhen Lina; Pang Da; Zhang Qingyuan (Clinical & Experimental Metastasis, 2013)

Seismic deformation and seismic resistance analysis of Shapai Roller Compacted Concrete Arch Dam based on field monitoring and dynamic finite element method - Li Zhuo; Jiang-da He; Hong-qiang Xie (Journal of Mountain Science, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

Effect of sinomenine on vascular smooth muscle cell dedifferentiation and neointima formation after vascular injury in mice - Lihua Zhu; Yarong Hao; Hongjing Guan; Changping Cui; Song Tian; Da Yang; Xinan Wang; Shuming Zhang; Lang Wang; Hong Jiang (Molecular and Cellular Biochemistry, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Low BDNF is associated with cognitive impairment in chronic patients with schizophrenia - Xiang Yang Zhang; Jun Liang; Da Chun Chen; Mei Hong Xiu; Fu De Yang; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2012)

Characterization and expression pattern of KIFC1-like kinesin gene in the testis of the Macrobrachium nipponense with discussion of its relationship with structure lamellar complex (LCx) and acroframosome (AFS) - Yan-Ting Wang; Huan Mao; Cong-Cong Hou; Xiao Sun; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Three new secolignan glycosides from Urtica fissa E. Pritz - Bao-min Feng; Hai-hong Qin; Hui-guo Wang; Li-ying Shi; Da-yong Yu; Bao-quan Ji; Qi Zhao; Yong-qi Wang (Journal of Natural Medicines, 2012)

Cognitive and serum BDNF correlates of BDNF Val66Met gene polymorphism in patients with schizophrenia and normal controls - Xiang Yang Zhang; Da Chun Chen; Mei Hong Xiu; Colin N. Haile; Xingguang Luo; Ke Xu; Hui Ping Zhang; Lingjun Zuo; Zhijun Zhang; Xiangrong Zhang; Therese A. Kosten; Thomas R. Kosten (Human Genetics, 2012)

Characterization and expression analysis of prohibitin in the testis of Chinese mitten crab Eriocheir sinensis - Huan Mao; Da-Hui Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Recognition of early Carboniferous alkaline granite in the southern Altai orogen: post-orogenic processes constrained by U–Pb zircon ages, Nd isotopes, and geochemical data - Ying Tong; Tao Wang; Wolfgang Siebel; Da-Wei Hong; Min Sun (International Journal of Earth Sciences, 2012)

A first set of polymorphic microsatellite loci isolated from Rhinogobio cylindricus - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen; Shao Ping Liu; Fan Rrong Zhang; Dong Yang; Lai Ning Yu (Conservation Genetics Resources, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Gene expression profiles of prohibitin in testes of Octopus tankahkeei (ot-phb) revealing its possible role during spermiogenesis - Hai-Tao Mao; Da-Hui Wang; Zhou Lan; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Secretory expression and characterization of a soluble laccase from the Ganoderma lucidum strain 7071-9 in Pichia pastoris - Jing Sun; Ri-He Peng; Ai-Sheng Xiong; Yongsheng Tian; Wei Zhao; Hu Xu; Da-Tong Liu; Jian-Min Chen; Quan-Hong Yao (Molecular Biology Reports, 2012)

Isolation and characterization of polymorphic microsatellite loci from elongate loach (Leptobotia elongate), a threatened fish species endemic to the Yangtze River - Hong Yan Liu; Fei Xiong; Xin Bin Duan; Da Qing Chen (Conservation Genetics Resources, 2012)

Important photosynthetic contribution from the non-foliar green organs in cotton at the late growth stage - Yuan-Yuan Hu; Ya-Li Zhang; Hong-Hai Luo; Wei Li; Riichi Oguchi; Da-Yong Fan; Wah Soon Chow; Wang-Feng Zhang (Planta, 2012)

Genome wide QTL mapping to identify candidate genes for carcass traits in Hanwoo (Korean Cattle) - Seung Hwan Lee; Julius van der Werf; Sang Hong Lee; Da Jeong Lim; Eung Woo Park; Cedric Gondro; Duhak Yoon; Sung Jong Oh; Oun Hyun Kim; John Gibson; John Thompson (Genes & Genomics, 2012)

A novel genus of multicellular magnetotactic prokaryotes from the Yellow Sea - Ke Zhou; Wen‐Yan Zhang; Kui Yu‐Zhang; Hong‐Miao Pan; Sheng‐Da Zhang; Wei‐Jia Zhang; Hai‐Dong Yue; Ying Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2012)
Summary Multicellular magnetotactic prokaryotes (MMPs) are a group of magnetotactic microorganisms composed of 10–40 Gram‐negative cells. Currently, all the identified MMPs show a spherical morphology and synthesize mainly iron sulfide magnetosomes. In this study, we report a novel genus of MMPs with peculiar ellipsoidal morphology and iron oxide magnetosomes, which were discovered in intertidal sediment of the Yellow Sea in China. Optical and fluorescence microscopy revealed that this organism was ∼10 × 8 µm in size and composed of ∼40 cells enveloped by an outer layer. Scanning electron microscopy showed that the cells were arranged in 4–6 interlaced circles. Bullet‐shaped magnetite magnetosomes were organized in chains roughly parallel to the long axis of the ellipsoidal MMPs when analysed by transmission electron microscopy. These MMPs displayed special escape motility, i.e. swimming rapidly from the edge to the centre of the droplet and then slowly back to the edge. In addition, they exhibited negative phototaxis. Light microscopy observations showed that the ellipsoidal MMPs reproduced by division along the body long axis. Both analysis of 16S rRNA gene sequence and fluorescence in situ hybridization revealed the ellipsoidal MMPs as a new genus of the Deltaproteobacteria . In summary, this novel genus of MMPs exhibit unique morphology, peculiar division process and distinct phylogenetic affiliation compared with the other MMPs.

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Mitochondrial DNA diversity of Glyptothorax zanaensis (Wu et al., 1981) populations in Nu River, China - Xi-Ping Yuan; Yuan-An Wu; Bo Hong; Deng-Qiang Wang; Shao-Ping Liu; Da-Qing Chen (Environmental Biology of Fishes, 2012)

Ototoxic destruction by co-administration of kanamycin and ethacrynic acid in rats - Hong Liu; Da-lian Ding; Hai-yan Jiang; Xue-wen Wu; Richard Salvi; Hong Sun (Journal of Zhejiang University-SCIENCE B, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

Metaproteomic characterization of dissolved organic matter in the water column of the South China Sea - Da-Zhi Wang; Hong-Po Dong; Zhang-Xian Xie; Min-Han Dai; Hua-Sheng Hong (Limnology and Oceanography, 2011)
We characterized dissolved organic matter (DOM;

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Chromosome numbers are not fixed in Agaonidae (Hymenoptera: Chalcidoidea) - Qing Liu; Xiao hong Ou; Stephen G. Compton; Da rong Yang (Symbiosis, 2011)

Molecular cloning and characterization of Izumo1 gene from sheep and cashmere goat reveal alternative splicing - Wan-Jin Xing; Bao-Da Han; Qi Wu; Li Zhao; Xiao-Hong Bao; Shorgan Bou (Molecular Biology Reports, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Wavelet estimation by matching well-log, VSP, and surface-seismic data - Hong-Da Ma; Roy E. White; Tian-Yue Hu (Applied Geophysics, 2010)

Polymorphisms in the calcineurin genes are associated with the training responsiveness of cardiac phenotypes in Chinese young adults - Zi-Hong He; Yang Hu; Yan-Chun Li; Da-Peng Bao; Jonatan R. Ruiz; Alejandro Lucia (European Journal of Applied Physiology, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Characterization of particulate organic matter in the water column of the South China Sea using a shotgun proteomic approach - Hong-Po Dong; Da-Zhi Wang; Minhan Dai; Hua-Sheng Hong (Limnology and Oceanography, 2010)
We characterized particulate organic matter (POM) collected from both the surface (41 m and 200 m) and mesopelagic layers (500 m and 1000 m) in the western South China Sea. By using a shotgun proteomic approach, a total of 3035 proteins matching one or more peptides were detected from four POM samples, 505 of which were identified as high‐confidence proteins matching two or more peptides. Cyanobacteria was the largest contributor throughout the water column, while crustaceans and dinophytes were the two major groups contributing to the particulate proteins in the POM collected from 200 m. Subcellular locations and biological processes of particulate proteins varied significantly between the 41‐m and 200‐m layers: photosynthesis‐associated proteins were highly abundant in the 41‐m layer while tubulins and actins accumulated in the midwaters, especially at the 200‐m layer. Porins, adenosine triphosphate synthases, nutrient transporters, molecular chaperones, and ectoenzymes were frequently detected in the POM samples and presented different distribution patterns within the water column, revealing complex biological processes at the different water layers and/or during the sinking of POM. The sources of surface and midwater particulate proteins are different, and the cellular metabolism, generation of energy, and transport processes in POM are attenuated rapidly down ocean water column. Zooplankton fecal pellet packages and membrane encapsulation might play important roles in protecting particulate proteins from degradation.

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Down-Regulation of Stat3 Decreases Invasion Activity and Induces Apoptosis of Human Glioma Cells - Fuxue Chen; Yaming Xu; Youqun Luo; Da Zheng; Yichao Song; Kangkang Yu; Hong Li; Li Zhang; Weiwei Zhong; Yonghua Ji (Journal of Molecular Neuroscience, 2010)

Evaluation of Pyrogallol-induced Cytotoxicity in Catalase-mutant Escherichia coli and Mutagenicity in Salmonella typhimurium - Yoko Takemura; Da-Hong Wang; Rani Sauriasari; Masako Horita; Ken Tsutsui; Kuniaki Sano; Noriyoshi Masuoka; Tomoko Takigawa; Jiro Takaki; Keiki Ogino (Bulletin of Environmental Contamination and Toxicology, 2010)

Isolation of a new glycoside from starfish, Asterias amurensis Lutken, and its stimulation activity on the proliferation of the UMR106 cell - Hong-Wei Liu; Jian-Kuan Li; Da-Wei Zhang; Jing-Chao Zhang; Xue Zhang; Xiao-Hong Song; Ying Xia; Nai-Li Wang; Xin-Sheng Yao; Guo-Ping Cai (Natural Product Research, 2010)

Mutational analysis of Arabidopsis PP2CA2 involved in abscisic acid signal transduction - Xin-Hong Guo; Ke-Qin Deng; Jie Wang; Da-Shi Yu; Qiong Zhao; Xuan-Ming Liu (Molecular Biology Reports, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Decreased levels of serum brain-derived neurotrophic factor in drug-naïve first-episode schizophrenia: relationship to clinical phenotypes - Da Chun Chen; Jing Wang; Bo Wang; Sheng Chang Yang; Chong Xi Zhang; You Lan Zheng; Yan Li Li; Ning Wang; Ke Bing Yang; Mei Hong Xiu; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2009)

Branco River Stage Gradient Determination and Amazon Hydrologic Studies Using GPS Water Level Measurements - Kai-Chien Cheng; Stephane Calmant; Chung-Yen Kuo; Hong-Zeng Tseng; C. K. Shum; Frederique Seyler; Joecila Santos Da Silva (Marine Geodesy, 2009)

Gender differences in the prevalence, risk and clinical correlates of tardive dyskinesia in Chinese schizophrenia - Xiang Yang Zhang; Da Chun Chen; Ling Yan Qi; Fang Wang; Mei Hong Xiu; Song Chen; Gui Ying Wu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Astragalus mongholicus ameliorates renal fibrosis by modulating HGF and TGF-β in rats with unilateral ureteral obstruction - Chuan Zuo; Xi-sheng Xie; Hong-yu Qiu; Yao Deng; Da Zhu; Jun-ming Fan (Journal of Zhejiang University-SCIENCE B, 2009)

Elevational patterns of species richness and endemism for some important taxa in the Hengduan Mountains, southwestern China - Da-Cai Zhang; Yong-Hong Zhang; David E. Boufford; Hang Sun (Biodiversity and Conservation, 2009)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Hyper-spectral remote sensing to monitor vegetation stress - Hong-Yan Ren; Da-Fang Zhuang; Jian-Jun Pan; Xue-Zheng Shi; Hong-Jie Wang (Journal of Soils and Sediments, 2008)

Polymorphic microsatellite loci for population studies of the razor clam, Sinonovacula constricta - Dong-Hong Niu; Jia-Le Li; Da-Bo Liu (Conservation Genetics, 2008)

Infection of green fluorescence protein-tagged Fusarium graminearum on wheat and barley spikes - Xu Zhang; Theo Lee; Marie Dufresne; Tai-guo Liu; Wei-zhong Lu; Da-zhao Yu; Hong-xiang Ma (Cereal Research Communications, 2008)

Analysis of quantitative trait loci underlying the period of reproductive growth stages in soybean (Glycine max [L.] Merr.) - Da-Wei Xin; Hong-Mei Qiu; Da-Peng Shan; Cai-Yun Shan; Chun-Yan Liu; Guo-Hua Hu; Christian Staehelin; Qing-Shan Chen (Euphytica, 2008)

Protective immunity of E. coli-synthesized NS1 protein of Japanese encephalitis virus - Cheng-Wen Lin; Kuang-Ting Liu; Hong-Da Huang; Wei-June Chen (Biotechnology Letters, 2008)

Development of an immunofluorescence technique for detecting Prorocentrum donghaiense Lu - Da-Zhi Wang; Xu-Guang Huang; Leo Lai Chan; Hua-Sheng Hong (Journal of Applied Phycology, 2007)

Glutathione S-transferases M1 and T1 polymorphisms and arsenic content in hair and urine in two ethnic clans exposed to indoor combustion of high arsenic coal in Southwest Guizhou, China - Guo-fang Lin; Hui Du; Ji-gang Chen; Hong-chao Lu; Jin-xiang Kai; Yun-shu Zhou; Wei-chao Guo; Xin-jiang Zhang; Da-ru Lu; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2007)

Association of functional catechol O-methyl transferase (COMT) Val108Met polymorphism with smoking severity and age of smoking initiation in Chinese male smokers - Song Guo; Da Fang Chen; Dong Feng Zhou; Hong Qiang Sun; Gui Ying Wu; Colin N. Haile; Therese A. Kosten; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2007)

Genetic diversity within Oryza rufipogon germplasms preserved in Chinese field gene banks of wild rice as revealed by microsatellite markers - Li-Zhi Gao; Chi-Hong Zhang; Dao-Yuan Li; Da-Jian Pan; Ji-Zeng Jia; Yu-Shen Dong (Biodiversity and Conservation, 2006)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Enhanced degradation of carbon tetrachloride by surfactant-modified zero-valent iron - Ya-feng Meng; Bao-hong Guan; Zhong-biao Wu; Da-hui Wang (Journal of Zhejiang University-SCIENCE B, 2006)

The style–length of the female florets and their fate in two dioecious species of Xishuangbanna, China - Zhang-Hong Shi; Da-Rong Yang; Yan-Qiong Peng (Trees, 2006)

Application of near-infrared spectroscopy to predict sweetpotato starch thermal properties and noodle quality - Guo-quan Lu; Hua-hong Huang; Da-peng Zhang (Journal of Zhejiang University-SCIENCE B, 2006)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)

New insights into the complex and coordinated transcriptional regulation networks underlying rice seed development through cDNA chip-based analysis - Ke Duan; Yong-Hai Luo; Da Luo; Zhi-Hong Xu; Hong-Wei Xue (Plant Molecular Biology, 2005)

pp5644 Interacts with phosphatidylinositol-4-phosphate adaptor protein-1 associated protein-1 - Xiao-Xia Ye; Hong Lu; Yao Yu; Ning Ding; Nai-Ling Zhang; Ke-Ke Huo; Da-Fang Wan; Yu-Yang Li; Jian-Ren Gu (Molecular and Cellular Biochemistry, 2005)

OsPIPK1, a Rice Phosphatidylinositol Monophosphate Kinase, Regulates Rice Heading by Modifying the Expression of Floral Induction Genes - Hui Ma; Shu-Ping Xu; Da Luo; Zhi-Hong Xu; Hong-Wei Xue (Plant Molecular Biology, 2004)

Phylogenetic Analysis Reveals that a Dwarfing Disease on Different Cereal Crops in China is due to Rice Black Streaked Dwarf Virus (RBSDV) - Feng-wei Bai; Jian Yan; Zhi-cai Qu; Hong-wei Zhang; Jia Xu; Ming-ming Ye; Da-leng Shen (Virus Genes, 2002)

Application of suppression subtractive hybridization (SSH) to cloning differentially expressed cDNA inDunaliella salina (chlorophyta) under hyperosmotic shock - Xiao-Ning Zhang; Zhi-Cai Qu; You-Zhong Wan; Hong-Wei Zhang; Da-Leng Shen (Plant Molecular Biology Reporter, 2002)

Light-induced increase in initial chlorophyll fluorescence Fo level and the reversible inactivation of PS II reaction centers in soybean leaves - Shuang-Song Hong; Da-Quan Xu (Photosynthesis Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Enhanced liver injury in acatalasemic mice following exposure to carbon tetrachloride - Da-Hong Wang; Kunihiko Ishii; Li-Xue Zhen; Kazuhisa Taketa (Archives of Toxicology, 1996)